Thermoplastic elastomer composition for pharmaceutical products
A thermoplastic elastomer composition using brominated isobutylene-p-methyl-styrene terpolymers and polypropylene homopolymers, cured with specific systems, addresses the challenges of extractables and leachables in pharmaceutical products, providing improved gas barrier and processability for injection molding.
Patent Information
- Application Number
- CN202180049640.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-12
- Filing Date
- 2021-05-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-05-11
AI Technical Summary
Existing thermoplastic elastomer compositions for pharmaceutical products face challenges in achieving low extractables and leachables, particularly in injection molding processes, due to the need for high cleanliness and compatibility with sensitive drugs, while maintaining properties like elasticity, needle puncture resistance, and dimensional stability.
A thermoplastic elastomer composition comprising brominated isobutylene-p-methyl-styrene terpolymers and polypropylene homopolymers, cured using phenolic, sulfur-based, or amine-based cure systems, with optional soft thermoplastic elastomers and processing oils, to enhance gas barrier properties and processability.
The composition exhibits improved gas barrier properties, self-sealing, low impact force, and reduced extractables, enabling injection molding of high-quality pharmaceutical products with enhanced thermal stability and reduced drug interactions.
Smart Images

Figure CN115885010B_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of priority to USSN 63 / 023,561, filed May 12, 2020, which is incorporated herein by reference. Technical Field
[0003] The present disclosure relates to thermoplastic elastomer compositions comprising brominated isobutylene-p-methyl-styrene terpolymers, one or more thermoplastic polyolefins, optionally one or more soft thermoplastic elastomers, and cure systems for forming such thermoplastic elastomer compositions suitable for use in pharmaceutical products. Background Art
[0004] Unlike traditional vulcanized rubber, thermoplastic elastomer is a rubber-like material that can be processed and recycled. When a thermoplastic elastomer includes vulcanized rubber, the plastic elastomer may also be referred to as a thermoplastic vulcanizate (TPV), which is defined as a thermoplastic elastomer with a chemically cross-linked rubber phase produced by dynamic vulcanization. Filled and vulcanized elastomers have been widely used in pharmaceutical packaging (e.g., medicinal plugs and seals) to preserve medicines, and therefore account for 50% of typical medicinal plugs. The cleanliness of elastomers is essential to ensure low levels of extractables and leachables. Therefore, end users are increasing demand for medicinal plugs and seals with lower levels of extractables and leachables, which puts pressure on plug manufacturers and raw material suppliers in the healthcare industry.
[0005] Preparation of elastomeric materials can be achieved by injection molding, transfer molding or compression molding. Most pharmaceutical stoppers are prepared using thermosetting materials by compression molding. Due to the challenging physical properties required for pharmaceutical stopper applications (thermosetting materials need to have a low enough viscosity and a fast enough curing time for injection molding), stopper manufacturers have been unable to use injection molding. However, if TPV materials for injection molding can be developed, the benefits will include less waste, higher cleanliness and lower labor costs.
[0006] Non-limiting examples of desirable elastomeric properties include: sealing and resealing performance, the ability to be punctured by a needle without significant disintegration, and maintaining physical dimensions and properties when a plug formed from the elastomer is sterilized by high temperature or radiation. Other semi-crystalline materials (such as plastics and thermoplastic elastomers) cannot match amorphous elastomers in terms of elasticity, needle puncture resistance, low impact force requirements, and dimensional stability.
[0007] The shift to elastomers and elastomeric compositions for pharmaceutical applications is driven by many factors, including the need for high cleanliness stoppers that are compatible with modern sensitive drugs, the use of high purity ingredients to minimize any chemical species that migrate from the stopper and interact with the drug (drug compatibility / turbidity), the use of low amounts of clean curing agents to ensure drug stability / compatibility, tight control of visible and invisible particulate contamination, and the need for low extractables / leachables. When elastomeric components come into direct or indirect contact with drug products, there can be risks to drug quality and / or patient safety. Elastomeric components used in drug packaging / delivery systems must be demonstrated to be suitable for their intended use based on protection, compatibility, performance, and safety.
[0008] The levels of extractables and leachables in stoppers for parenteral drug packaging are already strictly regulated. Testing procedures and requirements for elastomeric components can be found in Elastomeric Closures for Injections USP "381", which addresses many medical and pharmaceutical issues, including: difficult to puncture closures (excessive puncture force required can lead to needle slippage and subsequent needle stick injuries); poor septum self-sealing (causing leakage during fluid transfer, thereby creating hazardous work areas and waste, while compromising the preservation of the dosage form through evaporation, non-sterility, and drug deterioration); fragmentation (fragmentation after needle puncture of the septum can contaminate the contents and / or create a leak path); biocompatibility (based on in vitro and in vivo testing to ensure the absence of adverse biological effects). In addition to the basic requirements set forth in USP "381", elastomers will need to meet the intended use to be commensurate with the level of risk to drug product quality and patient safety. These evaluations will include studies of extractables and leachables. To achieve good drug compatibility and minimize extractables and leachables, stopper manufacturers typically use high-cleanliness raw materials, optimize formulations to contain minimal levels of curing agents and other additives, and comply with Good Manufacturing Practices (GMP) or other ISO standards.
[0009] Among the commercially available elastomers, halogenated butyl polymers (e.g., chlorobutyl rubber and bromobutyl rubber) remain the elastomer of choice for pharmaceutical stoppers and seals worldwide because of their relatively high cleanliness, high gas and moisture barrier properties, and low levels of additives and impurities. In addition, due to the universal curing properties of halogenated butyl rubber elastomers, halogenated butyl polymers are now primarily used to replace conventional butyl rubber to prepare high-quality pharmaceutical stoppers. Conventional butyl rubber requires high levels of sulfur-containing and / or zinc-containing curing agents, which is unacceptable. Bromobutyl rubber elastomers can be cured using low levels of zinc-free and sulfur-free curing agents, thus providing a high degree of cleanliness.
[0010] Brominated isobutylene p-methylstyrene (BIMSM) elastomer is a very clean elastomer that has been adopted by industry to manufacture plugs for packaging expensive drugs such as antibiotics, water for injection, vaccines and biological products. Unlike halogenated butyl rubber, BIMSM elastomer has a fully saturated main chain, so butylated hydroxylated toluene (BHT) or other antioxidants and stabilizers (such as epoxidized soybean oil (ESBO)) are not required to stabilize. The polymer does not contain oligomers that are byproducts in butyl polymerization and halogenated butyl polymerization processes. BHT, oligomers and other additives have been found to be extractables, which can cause drug incompatibilities with antibiotics and other sensitive drugs. Due to the "latex sensitivity" problem, the use of natural rubber is limited. The use of other synthetic rubbers is hindered by high air permeability and moisture permeability, poor oxidation resistance and poor heat resistance.
[0011] In addition to additives and byproducts in the elastomer composition, the curing agent used for vulcanization is also a major source of extractables for pharmaceutical stoppers. BIMSM can be effectively crosslinked through the benzyl bromide functional group and requires less curing agent than halogenated butyl rubber to achieve effective crosslinking. However, any curing agent and processing additive used has the potential to be extracted and cause drug incompatibility with sensitive drugs and biologics. However, it remains a challenge to develop an optimized curing system that will help improve the properties of thermoplastic elastomers while preventing any adverse drug interactions.
[0012] Therefore, it is necessary to simplify the process of producing pharmaceutical plugs and other medical products by using the thermoplastic elastomer composition of the present invention. The thermoplastic elastomer composition described in this article can be processed by traditional high-yield thermoplastic processes (such as injection molding or extrusion). The prior art aimed at solving this challenge has adopted a thermoplastic elastomer compound, which contains a hydrogenated derivative of a block copolymer composed of an aromatic vinyl compound and a conjugated diene, a rubber softener, and an olefin-based resin; however, this rubber plug exhibits a higher permeability coefficient, thereby resulting in insufficient gas barrier properties for the contained fluid. The present invention solves the challenge of producing medical sealing products, which are prepared by using thermoplastic elastomers and thermoplastic vulcanizates and show improved gas barrier properties, self-sealing properties and low impact force.
[0013] The present invention also describes a medical container stopper composed of a thermoplastic vulcanizate obtained by dynamic crosslinking of a BIMSM elastomer in the presence of a thermoplastic phase and a "soft thermoplastic elastomer" phase. In addition, the BIMSM elastomer in the thermoplastic elastomer is crosslinked using a curing system that exhibits good processability and reduced extractables for pharmaceutical products. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A comparison of the self-sealing, fragmentation and punching properties of the compositions of the present invention is shown.
[0015] Figure 2 A comparison of % stress relaxation versus time is shown for compositions of the present invention.
[0016] Figure 3 A comparison of the ultimate % stress relaxation for the compositions of the present invention is shown. Summary of the invention
[0017] The present disclosure relates to a thermoplastic elastomer composition comprising one or more brominated isobutylene p-methyl-styrene terpolymers and a polypropylene homopolymer for use in pharmaceutical products comprising blends of such homopolymers and terpolymers.
[0018] The present disclosure also relates to a thermoplastic elastomer composition comprising: one or more brominated isobutylene para-methyl-styrene terpolymers; and 10 to 50 parts by weight or 10 to 80 parts by weight of a polypropylene homopolymer per hundred parts by weight of rubber (phr); wherein the thermoplastic elastomer composition is cured using a phenolic resin-based cure system, a sulfur-based cure system, or an amine-based cure system.
[0019] The present disclosure also relates to a thermoplastic elastomer composition comprising: one or more brominated isobutylene para-methyl-styrene terpolymers; 10 to 50 parts by weight or 10 to 80 parts by weight of a polypropylene homopolymer per hundred parts by weight of rubber (phr); and 10 to 100 phr of a process oil comprising a polyisobutylene polymer; wherein the thermoplastic elastomer composition is cured using a phenolic resin-based cure system, a sulfur-based cure system, or an amine-based cure system; and wherein the thermoplastic elastomer composition has a hardness (Shore A) of 40 to 90, or 20 to 90.
[0020] The present disclosure also relates to a thermoplastic elastomer composition comprising one or more at least partially crosslinked brominated isobutylene p-methyl-styrene terpolymers and a polypropylene homopolymer for use in a pharmaceutical product comprising a blend of such terpolymers and homopolymers.
[0021] The present disclosure also relates to a thermoplastic vulcanizate composition comprising: an elastomeric phase comprising one or more brominated isobutylene para-methyl-styrene terpolymers; 10 to 90 parts by weight per hundred parts by weight of rubber (phr) of a thermoplastic phase comprising a blend of one or more thermoplastic polyolefins and one or more soft thermoplastic elastomers, wherein the soft thermoplastic elastomer has a Shore A hardness of 20 to 96, a Shore D hardness of 20 to 50, and a tensile strength at break of 2 MPa to 20 MPa; and 10 to 100 phr of a processing oil; wherein the elastomeric phase is cured using a phenolic resin-based cure system or an amine-based cure system.
[0022] The present disclosure is also directed to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise an olefin-based block copolymer comprising crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, wherein the crystallizable ethylene-octene blocks have an α-olefin comonomer content of less than 10 wt % and a melting point greater than 90° C., and the low crystallinity ethylene-octene blocks have a comonomer content of greater than 10 wt % and a melting point less than 90° C.
[0023] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise a propylene based olefin block copolymer (OCP) blend comprising an ethylene-propylene (EP) copolymer, an isotactic polypropylene (iPP) and an EP-iPP diblock polymer.
[0024] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise a styrene-isobutylene styrene (SIBS) polymer.
[0025] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise a propylene-based elastomer comprising units derived from a major portion of propylene and from about 5 wt % to about 25 wt % of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins.
[0026] The present disclosure also relates to a thermoplastic vulcanizate composition, wherein the one or more soft thermoplastic elastomers comprise a 4-methyl-1-pentene / α-olefin copolymer, the 4-methyl-1-pentene / α-olefin copolymer comprising 50 wt % to 100 wt % of structural units derived from methyl-1-pentene, and 0 wt % to 50 wt % of structural units derived from at least one olefin selected from olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene.
[0027] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more thermoplastic polyolefins comprise a propylene-based polymer, an ethylene-based thermoplastic polymer, a polypropylene homopolymer (PPH), or any combination thereof.
[0028] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the elastomeric phase is cured using an amine cure system comprising one or more amine curing agents present in an amount of 0.1 to 10 phr, and wherein the one or more amine curing agents are selected from (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
[0029] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the cure system is substantially free of heavy metal components, phenolic resins, or sulfur.
[0030] The present disclosure also relates to a thermoplastic vulcanizate composition further comprising a cyclopentadiene-based hydrocarbon resin having a glass transition temperature (Tg) greater than 20°C.
[0031] The present disclosure also relates to a thermoplastic vulcanizate composition that exhibits improved coring performance, self-sealing, low punch force, excellent oxygen barrier properties, and improved compression set at high temperatures.
[0032] The present disclosure also relates to the above-mentioned thermoplastic vulcanizate composition, which exhibits a Shore A hardness in the range of 20 to 90, a tensile strength at break of 1.5 MPa to 8 MPa, a compression set at 70°C of <35%, and an oxygen permeability measured at 40°C of <0.2cc*mm / (m2-day-mmHg). DETAILED DESCRIPTION
[0033] The present disclosure relates to a thermoplastic elastomer composition comprising one or more brominated isobutylene para-methyl-styrene terpolymers (BIMSM) and polypropylene homopolymer (PPH) suitable for use in pharmaceutical articles and other articles comprising a blend of such PPH and one or more BIMSMs.
[0034] Embodiments of the present disclosure include thermoplastic elastomer compositions comprising a blend of (a) one or more BIMSMs, and (b) 20 to 50 parts by weight or 15 to 90 parts by weight of PPH per hundred parts by weight of rubber (phr), wherein the thermoplastic elastomer composition is cured using a phenolic resin-based cure system, a sulfur-based cure system, or an amine-based cure system.
[0035] Preferably, the PPH has a melt flow rate (MFR) (230°C / 2.16kg) of 0.5 g / 10min to 2000 g / 10min (or 0.5 g / 10min to 1500 g / 10min, or 0.5 g / 10min to 1000 g / 10min, or 0.5 g / 10min to 500 g / 10min, or 0.5 g / 10min to 100 g / 10min, more preferably 0.5 g / 10min to 20 g / 10min) based on ASTM D1238 test method. Preferably, the one or more BIMSMs are brominated copolymers of isobutylene and p-methyl-styrene having a Mooney viscosity (ML 1+8, 125°C) of 30 MU to 50 MU according to ASTM D1646 test method and / or a benzyl bromide content of 0.3 mol% to 5 mol%.
[0036] Embodiments of the present disclosure further include thermoplastic elastomer compositions comprising a blend of: (a) one or more BIMSMs; (b) 20 to 50 parts by weight or 10 to 90 parts by weight of a thermoplastic polyolefin per hundred parts by weight of rubber (phr); (c) one or more curing agents (e.g., present at 0.1 to 15 phr or 0.5 to 10 phr); and (d) a processing oil (e.g., present at 40 to 80 phr or 50 to 70 phr), wherein the thermoplastic elastomer composition is cured using a phenolic resin-based cure system, a ZnO-initiated alkylation cure system, a sulfur-based cure system, or an amine-based cure system.
[0037] The present disclosure also relates to a thermoplastic vulcanizate composition comprising: an elastomeric phase comprising one or more brominated isobutylene para-methyl-styrene terpolymers; 10 to 90 parts by weight per hundred parts by weight of rubber (phr) of a thermoplastic phase comprising a blend of one or more thermoplastic polyolefins and one or more soft thermoplastic elastomers, wherein the soft thermoplastic elastomer has a Shore A hardness of 20 to 96, a Shore D hardness of 20 to 50, and a tensile strength at break of 2 MPa to 20 MPa; and 10 to 100 phr of a processing oil; wherein the elastomeric phase is cured using a phenolic resin-based cure system or an amine-based cure system.
[0038] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise an olefin based block copolymer (OBC) comprising crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, wherein the crystallizable ethylene-octene blocks have an α-olefin comonomer content of less than 10 wt % and a melting point greater than 90° C., and the low crystallinity ethylene-octene blocks have a comonomer content of greater than 10 wt % and a melting point less than 90° C. Preferably, the OBC has a melt flow rate (MFR) (190°C / 2.16kg) of 0.5 g / 10min to 30 g / 10min (most preferably 0.5 g / 10min to 6 g / 10min), a density of 0.85 g / ml to 0.90 g / ml (most preferably 0.860 g / ml to 0.880 g / ml), a melting point of 100°C to 130°C (most preferably 115°C to 125°C), a Shore A hardness of 30 to 95 (most preferably 50 to 85), a tensile strength of 1.5 MPa to 18 MPa (most preferably 2 MPa to 15 MPa), and a compression set at 70°C of 20% to 120% (most preferably 40% to 100%).
[0039] The present disclosure also relates to a thermoplastic vulcanizate rubber composition, wherein one or more soft thermoplastic elastomers include propylene-based olefin block copolymer (OCP, propylene based olefin block copolymer) blends, and the propylene-based olefin block copolymer (OCP) blends include ethylene-propylene (EP) copolymers, isotactic polypropylene (iPP) and EP-iPP diblock polymers. Preferably, the melt flow rate (MFR) (230°C / 2.16kg) of the OBC blend is 0.5 to 100g / 10min (or 1g / 10min to 75g / 10min, or 2g / 10min to 50g / 10min, or 3g / 10min to 40g / 10min, based on ASTM D1238 test method). Preferably, the OBC blend exhibits a Shore A hardness of 30 to 98 (or 40 to 95, 50 to 95, 60 to 95). Preferably, the OBC blend exhibits a Shore D hardness of 5 to 60 (or 10 to 55, 15 to 50, 15 to 45). Preferably, the OBC blend exhibits an ethylene content of 90 wt% to 15 wt% (or 85 wt% to 20 wt%, 80 wt% to 25 wt%, 77 wt% to 30 wt%). Preferably, the OBC blend exhibits a Vicat softening point of 20°C to 150°C (or 30°C to 140°C, 40°C to 135°C, 50°C to 130°C). Preferably, the OBC blend exhibits a tensile strength at break of 1.5 MPa to 20 MPa (or 2 MPa to 18 MPa, or 2 MPa to 17 MPa, or 2.5 MPa to 16 MPa).
[0040] The present disclosure also relates to a thermoplastic vulcanizate composition, wherein one or more soft thermoplastic elastomers include styrene-isobutylene styrene (SIBS) polymers. Preferably, the melt flow rate (MFR) (230°C / 2.16kg) of the SIBS polymer is 0.05g / 10min to 30g / 10min (most preferably 0.1g / 10min to 25g / 10min), the tensile strength at break is 4MPa to 25MPa (preferably 6MPa to 20MPa), the Shore A hardness is 15 to 60 (most preferably 20 to 50), and the compression deformation at 70°C is 30% to 120% (most preferably 48% to 96%). SIBS polymers can also be used instead of polybutene oil.
[0041] The present disclosure also relates to a thermoplastic vulcanizate composition, wherein one or more soft thermoplastic elastomers comprise a propylene-based elastomer containing units derived from a major portion of propylene and about 5 wt% to about 25 wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins. Preferably, the propylene-based elastomer has a melt flow rate (MFR) (190°C / 2.16kg) of 0.2 g / 10min to 25 g / 10min (most preferably 0.5 g / 10min to 20 g / 10min), and an ethylene content of 1 wt% to 25 wt% (most preferably 3 wt% to 19 wt%).
[0042] The present disclosure also relates to a thermoplastic vulcanizate composition, wherein the one or more soft thermoplastic elastomers contain 50 wt% to 100 wt% of structural units derived from methyl-1-pentene, and 0 wt% to 50 wt% of structural units derived from at least one olefin selected from olefins other than 4-methyl-1-pentene having 2 to 20 carbon atoms. Preferably, the 4-methyl-1-pentene copolymer has an MFR (230° C., 2.16 kg) of 0.5 g / 10 min to 20 g / 10 min (most preferably 2 g / 10 min to 15 g / 10 min), a tensile strength at break of 20 MPa to 30 MPa (most preferably 25 MPa to 35 MPa), and a Tg of -10° C. to 50° C. (most preferably 10° C. to 40° C.).
[0043] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more soft thermoplastic elastomers comprise:
[0044] (1) an olefin-based block copolymer comprising crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, wherein the crystallizable ethylene-octene blocks have an α-olefin comonomer content of less than 10 wt% and a melting point of greater than 90°C, and the low crystallinity ethylene-octene blocks have a comonomer content of greater than 10 wt% and a melting point of less than 90°C,
[0045] (2) a propylene-based olefin block copolymer (OCP) blend comprising an ethylene-propylene (EP) copolymer, an isotactic polypropylene (iPP) and an EP-iPP diblock polymer,
[0046] (3) Styrene-isobutylene styrene (SIBS) polymer,
[0047] (4) a propylene-based elastomer comprising units derived from a major portion of propylene and from about 5 wt% to about 25 wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins, and
[0048] (5) a 4-methyl-1-pentene / α-olefin copolymer comprising 50% by weight to 100% by weight of a structural unit derived from 4-methyl-1-pentene and 0% by weight to 50% by weight of a structural unit derived from at least one olefin selected from olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene,
[0049] or any combination thereof.
[0050] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the one or more thermoplastic polyolefins comprise a propylene-based polymer, an ethylene-based thermoplastic polymer, a polypropylene homopolymer (PPH), or any combination thereof.
[0051] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the elastomeric phase is cured using an amine cure system comprising one or more amine curing agents present in an amount of 0.1 to 10 phr, and wherein the one or more amine curing agents are selected from (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
[0052] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the vulcanization system is substantially free of heavy metal components, phenolic resins, or sulfur, in compliance with FDA 21 CFR 177.2600.
[0053] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the processing oil comprises a polyisobutylene polymer.
[0054] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the processing oil comprises a propylene-based elastomer comprising units derived from a major portion of propylene and from about 5 wt % to about 25 wt % of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins.
[0055] The present disclosure also relates to a thermoplastic vulcanizate composition further comprising a cyclopentadiene-based hydrocarbon resin having a glass transition temperature (Tg) greater than 20°C.
[0056] The present disclosure also relates to a thermoplastic vulcanizate composition wherein the elastomeric phase is at least partially crosslinked.
[0057] Embodiments of the present disclosure further include thermoplastic vulcanizates that exhibit a Shore A hardness of 20 to 90, a tensile strength at break of 1.5 MPa to 8 MPa, a compression set at 70° C. of <35%, and an oxygen permeability measured at 40° C. of <0.2 cc*mm / (m2-day-mmHg).
[0058] Advantageously, such thermoplastic elastomer compositions provide improved physical properties required for pharmaceutical stopper applications, such as higher resistance to thermal degradation, better post-curing elasticity, enhanced aging and abrasion resistance, stronger gas barrier, good coring performance and resealing behavior, improved low permeability, enhanced resealing, low fragmentation, enhanced toughness, improved melt flow and injection molding capabilities, and improved leachable properties, compared to conventional TPVs or thermosetting rubbers. Due to these improved properties, the thermoplastic elastomer compositions described herein can be used to produce higher quality pharmaceutical products.
[0059] The present disclosure also relates to a method for preparing the aforementioned thermoplastic elastomer and thermoplastic vulcanizate composition, comprising: blending a thermoplastic phase with one or more BIMSM, a curing agent (also referred to as "curative") suitable for use in a phenolic resin-based curing system, a sulfur-based curing system or an amine-based curing system, a processing oil, and optional other additives. Preferably, the processing oil comprises a polyisobutylene polymer.
[0060] The thermoplastic elastomer composition can be used for pharmaceutical applications to improve physical properties, such as permeability, resealability, fragmentation, toughness, melt flow and injection molding ability and leachables. The thermoplastic vulcanizate composition of the present invention is based on BIMSM, a thermoplastic phase comprising a thermoplastic polyolefin and a soft thermoplastic elastomer, a processing oil and a curing agent, which provides gas barrier properties and compression deformation properties comparable to butyl rubber. Therefore, due to the advantage of being able to be injection molded, plastic products can be made from the formulation of the present invention for seals, closures and other products previously made with butyl rubber, particularly medical container seals, syringe tips, syringe plunger tips, penetrable diaphragms, stoppers, bottle caps and plugs. Other products (such as the following industrial products and consumer products: food and beverage container seals, printer cartridge seals and other products requiring flexibility and barrier properties) can be made from the thermoplastic elastomer composition of the present invention as a suitable substitute for butyl rubber.
[0061] Definition and test methods
[0062] The new numbering scheme for the Periodic Table Groups is used as described in Chemical and Engineering News, 63(5), 27 (1985).
[0063] Unless otherwise stated, room temperature is 23°C.
[0064] The following abbreviations are used herein: PPH is polypropylene homopolymer; BIMSM is brominated isobutylene p-methyl-styrene; PIB is polyisobutylene; MFR is melt flow rate; Me is methyl; iPr is isopropyl; Ph is phenyl; wt% is weight percentage; mol% is mole percentage.
[0065] "Olefins", or "alkene", are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond.
[0066] "Polymer" has two or more identical or different monomeric units. "Homopolymer" is a polymer having identical monomeric units. The term "polymer" as used herein includes, but is not limited to, homopolymers, copolymers, terpolymers, etc. The term "polymer" as used herein also includes impact copolymers, block copolymers, graft copolymers, and alternating copolymers. Unless otherwise expressly stated, the term "polymer" shall further include all possible geometric configurations. Such configurations may include isotactic, syndiotactic, and random symmetry.
[0067] The term "blend" as used herein refers to a mixture of two or more polymers. The blend can be produced by, for example, solution blending, melt mixing, or compounding in a shear mixer. Solution blending is commonly used to prepare adhesive formulations comprising packaged butyl rubber, tackifier, and oil. The solution blend is then applied to a fabric substrate and the solvent evaporated to leave the adhesive.
[0068] As used herein, the term "monomer" or "comonomer" can refer to the monomer used to form the polymer (i.e., in the form of an unreacted chemical compound prior to polymerization), or it can refer to the monomer after incorporation into the polymer, also referred to herein as a "[monomer] derived unit." Various monomers are discussed herein, including propylene monomers, ethylene monomers, and diene monomers.
[0069] "Different" as used to refer to monomeric units means that the monomeric units differ from each other by at least one atom or are isomerically different.
[0070] As used herein, when a polymer is referred to as "comprising, consisting of, or consisting essentially of a monomer or a monomer-derived unit," the monomer is present in the polymer in the polymerized / derivative form of the monomer. For example, when a copolymer is considered to have an "isobutylene" content of 35 wt% to 55 wt%, it is understood that the monomer units in the copolymer are derived from isobutylene in the polymerization reaction, and the derived units are present at 35 wt% to 55 wt% based on the weight of the copolymer.
[0071] The molar ratio of the first olefin comonomer-derived units to the second olefin comonomer-derived units is 1 H NMR is measured, in which the different chemical shifts of the hydrogen atoms can be associated with each comonomer. The relative intensity of the NMR associated with the hydrogen then provides the relative concentration of each comonomer.
[0072] As used herein, "thermoplastic phase" refers to a solid, generally high molecular weight polymer plastic material, which may be referred to as a thermoplastic resin. The resin is a crystalline polymer or a semi-crystalline polymer, and may be a resin having a crystallinity of at least 25% as measured by differential scanning calorimetry. It is also acceptable for polymers with a high glass transition temperature to be used as a thermoplastic resin. In one or more embodiments, the melting temperature of these resins should be below the decomposition temperature of the rubber. Reference to a thermoplastic resin will include a thermoplastic resin or a mixture of two or more thermoplastic resins. As further described in this specification, the thermoplastic phase may also include a soft thermoplastic elastomer.
[0073] As used herein, "soft thermoplastic elastomer" refers to a thermoplastic elastomer with a Shore A hardness ranging from 20 to 96 and 20 to 50 when measured on the Shore D scale, and a tensile strength at break of 2 MPa to 20 MPa. Examples of soft thermoplastic elastomers are further described in the specification.
[0074] As used herein, "thermoplastic polyolefin" refers to polymers formed by polymerizing α-olefins (such as ethylene, propylene, 1-butene, 1-hexene, 1-octene, 2-methyl-1-propylene, 3-methyl-1-pentene, 4-methyl-1-pentene, 5-methyl-1-hexene, and mixtures thereof). Copolymers of ethylene and propylene or ethylene or propylene with another α-olefin (such as 1-butene, 1-hexene, 1-octene, 2-methyl-1-propylene, 3-methyl-1-pentene, 4-methyl-1-pentene, 5-methyl-1-hexene, or mixtures thereof) are also contemplated. These homopolymers and copolymers can be synthesized using any polymerization technique known in the art, such as, but not limited to, "Phillips catalysis", conventional Ziegler-Natta type polymerization, and metallocene catalysis (including, but not limited to, metallocene-aluminoxane and metallocene ion activator catalysis). Suitable catalyst systems therefore include chiral metallocene catalyst systems (see, for example, US Pat. No. 5,441,920) as well as transition metal-centered heteroaryl ligand catalyst systems (see, for example, US Pat. No. 6,960,635).
[0075] In one or more embodiments, the thermoplastic resin is a highly crystalline isotactic or syndiotactic polypropylene. These propylene polymers include both homopolymers of propylene, copolymers of propylene with 0.1wt% to 30wt% of ethylene or C4-C8 comonomers, and blends of such polypropylene. Polypropylene typically has a density of about 0.85g / cc to about 0.91g / cc, with most of the isotactic polypropylene having a density of about 0.90g / cc to about 0.91g / cc. In addition, high molecular weight and ultra-high molecular weight polypropylene with low melt flow rate or even fractional melt flow rate can be used.
[0076] Thermoplastic polyolefin resins may have an Mw of about 200,000 to about 700,000 and an Mn of about 80,000 to about 200,000. These resins may have an Mw of about 300,000 to about 600,000 and an Mn of about 90,000 to about 150,000.
[0077] The thermoplastic polyolefin resins may have a melting temperature (Tm) of about 150° C. to about 175° C., or about 155° C. to about 170° C., or about 160° C. to about 170° C. The glass transition temperature (Tg) of these resins is about −5° C. to about 10° C., or about −3° C. to about 5° C., or about 0° C. to about 2° C. The crystallization temperature (Tc) of these resins is about 95° C. to about 130° C., or about 100° C. to about 120° C., or about 105° C. to about 115° C., as measured by DSC and cooled at 10° C. / min.
[0078] These thermoplastic polyolefin resins can generally have a melt flow rate of up to 400 g / 10 min, but the thermoplastic vulcanizates of the present invention generally have better performance in many applications when the melt flow rate is less than about 30 g / 10 min, preferably less than 10 g / 10 min, or less than about 2 g / 10 min, or less than about 0.8 g / 10 min. The melt flow rate is a measure of the ease with which a polymer flows under standard pressure and is measured using ASTM D-1238 at 230°C and a 2.16 kg load.
[0079] In addition to crystalline or semi-crystalline or crystallizable polyolefins, other exemplary thermoplastic resins include polyimides, polyesters (nylons), poly(phenylene ethers), polycarbonates, styrene-acrylonitrile copolymers, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polystyrene derivatives, polyphenylene ethers, polyoxymethylenes, and fluorinated thermoplastics. The molecular weight is generally comparable to that of the thermoplastic polyolefin, but the melting temperature can be much higher. Therefore, the melting temperature of the selected thermoplastic resin should not exceed the temperature at which the rubber will decompose (i.e., when its molecular bonds begin to break or break so that the molecular weight of the rubber begins to decrease).
[0080] As used herein, "polypropylene homopolymer" (PPH) is a resin defined as a thermoplastic polymer produced by polymerization of propylene monomers. PPH can be isotactic polypropylene, highly isotactic polypropylene, or syndiotactic polypropylene. PPH can have a melt flow rate (MFR) (230°C / 2.16kg) of 0.5 g / 10 min to 2000 g / 10 min measured according to ASTM D1238 test method.
[0081] As used herein, the term "brominated isobutylene p-methyl-styrene terpolymer" (BIMSM) includes brominated copolymers of isobutylene and p-methyl-styrene.
[0082] As used herein, "phr" means "parts per hundred parts of rubber", where "rubber" is the total rubber content of the composition. In this article, only BIMSM is considered to contribute to the total rubber content. Thus, for example, a composition having 40 parts by weight of polypropylene homopolymer for every 100 parts by weight of BIMSM can be referred to as having 40 phr of polypropylene homopolymer. Other components added to the composition are calculated on a phr basis. For example, adding 50 phr of oil to the composition means that there are 50 g of oil in the composition for every 100 g of BIMSM. Unless otherwise stated, phr should be considered as phr by weight.
[0083] Rubber refers to any polymer or combination of polymers that meets the definition of ASTM D1566 as: "a material capable of recovering from substantial deformations and which is or has been modified to be substantially insoluble in boiling solvents (but which is capable of swelling)". Elastomer is a term used interchangeably with the term rubber.
[0084] An elastomeric composition is understood to mean any composition comprising at least one elastomer as defined above.
[0085] ASTM D1566 defines a vulcanized rubber compound as "a cross-linked elastomeric material compounded from elastomers which readily deforms to a greater extent under the action of a relatively small force and which recovers rapidly and forcefully to approximately its original size and shape after the deforming force is removed". A cured elastomeric composition is any elastomeric composition that has undergone a curing process and / or contains or is produced using an effective amount of a curing agent or a curing package and is a term used interchangeably with the term vulcanized rubber compound.
[0086] Thermoplastic elastomers, as defined by ASTM D1566, are rubbery materials that "can be repeatedly heated to soften and cooled to harden within the characteristic temperature range of the polymer, and can be molded into articles in the softened state." Thermoplastic elastomers can be microphase separation systems of at least two polymers. One phase is a hard polymer that does not flow at room temperature but becomes fluid when heated, giving the thermoplastic elastomer strength. The other phase is a soft rubbery polymer that gives the thermoplastic elastomer its elasticity. The hard phase is usually the main phase or continuous phase.
[0087] ASTM D1566 defines thermoplastic vulcanizates as "thermoplastic elastomers having a chemically crosslinked rubber phase produced by dynamic vulcanization". Dynamic vulcanization is "the process of intimately melt mixing a thermoplastic polymer with a suitable reactive rubbery polymer to produce a thermoplastic elastomer having a chemically crosslinked rubbery phase". The rubbery phase, whether crosslinked or not, is usually a minor or dispersed phase.
[0088] As used herein, "tensile strength" refers to the amount of stress applied to a sample to break the sample. It can be expressed in Pascals or pounds per square inch (psi). ASTM D412-16 can be used to determine the tensile strength of a polymer.
[0089] As used herein, "Mooney viscosity" is the Mooney viscosity of a polymer or polymer composition. The polymer composition analyzed for the determination of Mooney viscosity should be substantially free of solvent. For example, according to laboratory analysis techniques, the sample can be placed on a boiling water steam table in a fume hood to evaporate most of the solvent and unreacted monomers, and then dried overnight (12 hours, 90°C) in a vacuum oven before testing, or the sample for testing can be obtained from the polymer from which the volatile components are removed (i.e., the polymer after the volatile components are removed in an industrial scale process). Unless otherwise stated, the Mooney viscosity is measured using a Mooney viscometer according to ASTM D1646-17 but with the following modifications / explanations to the procedure. First, before testing, the sample polymer is squeezed between two hot plates of a compressor. The temperature of the plate is 125°C + / - 10°C, rather than the 50°C + / - 5°C recommended in ASTM D1646-17, because 50°C cannot produce enough mass. Furthermore, although ASTM D1646-17 allows for multiple options for mold protection, if any two options provide conflicting results, 36 micron PET should be used for mold protection. In addition, ASTM D1646-17 does not specify sample weight in Section 8; therefore, to the extent that results can vary with sample weight, the Mooney viscosity determined using the D1646-17 Section 8 procedure using a sample weight of 21.5 g + / - 2.7 g shall prevail. Finally, the pre-test resting procedure specified in D1646-17 Section 8 is 30 minutes at 23°C + / - 3°C in air; whereas the Mooney values reported herein are determined after 30 minutes of resting at 24°C + / - 3°C in air. The samples are placed on either side of the rotor according to the ASTM D1646-17 test method; the torque required to turn the viscometer motor at 2 rpm is measured by the transducer used to determine the Mooney viscosity. Results are reported as Mooney units (ML, 1+4, at 125°C), where M represents the Mooney viscosity number, L represents the large rotor (defined as ML in ASTM D1646-17), 1 represents the warm-up time in minutes, 4 represents the sample run time after motor start-up in minutes, and 125°C represents the test temperature. Thus, a Mooney viscosity of 90 determined by the method described above would be reported as a Mooney viscosity of 90MU (ML, 1+4, at 125°C). Alternatively, the Mooney viscosity may be reported as 90MU; in this case, it should be assumed that this viscosity was determined using the method just described unless otherwise stated. In some cases, a lower test temperature (e.g., 100°C) may be used, in which case the Mooney is reported as the Mooney viscosity (ML, 1+4, at 100°C), or at T°C, where T represents the test temperature.
[0090] The compression set of a material is the permanent deformation that remains after the compressive stress is released. The compression set of a material depends on the crosslink density of the material, which is defined as the torque difference between the maximum torque (also called "MH") and the minimum torque (also called "ML"). MH, ML and the torque difference "MH-ML" are evaluated by the Moving Die Rheometer (MDR) test method, a standard test method for rubber curing. MDR can be measured by the ASTM D5289 method and is usually reported in tenths of Newton meters (dN.m).
[0091] Numerical ranges used herein include the values recited within the range. For example, a numerical range of "1 wt % to 10 wt %" includes 1 wt % and 10 wt % within the range.
[0092] Unless otherwise indicated, all numbers used in this specification and the associated claims expressing quantities of ingredients, properties (such as molecular weight), reaction conditions, etc. are to be understood as being modified in all instances by the term "about". Therefore, unless otherwise indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that may vary depending on the desired properties sought to be obtained by embodiments of the present invention. At least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0093] One or more illustrative embodiments in conjunction with the invention embodiments disclosed herein are presented herein. For the sake of clarity, the present application does not describe or show all features of physical implementation. It is understood that in the development of the physical implementation in conjunction with the embodiments of the present invention, a large number of implementation-specific decisions need to be made to achieve the developer's goal, such as meeting system-related, business-related, government-related and other constraints, which are implemented and change from time to time. Although the developer's efforts may be time-consuming, such efforts will be routine work for those of ordinary skill in the art and benefit from the disclosure.
[0094] Although compositions and methods are described herein with the terms "comprising" or "having" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.
[0095] Thermoplastic elastomer compositions and compounding
[0096] The thermoplastic elastomer composition described herein comprises: one or more BIMSMs having a Mooney viscosity (ML 1+8, 125° C.) of 30 MU to 50 MU according to ASTM D1646 test method, and / or a benzyl bromide content of 0.3 mol % to 5 mol %; 20 phr to 50 phr of PPH having a D1238 test method of 0.5g / 10min to 2000g / 10min (or 0.5g / 10min to 1500g / 10min, or 0.5g / 10min to 1000g / 10min, or 0.5g / 10min to 500g / 10min, or 0.5g / 10min to 100g / 10min, more preferably 0.5g / 10min to 20g / 10min) melt flow rate (MFR) (230°C / 2.16kg); one or more curing agents; and processing oil (for example, present at 40phr to 80phr or 50phr to 70phr), and wherein the thermoplastic elastomer composition is cured using a phenolic resin-based curing system, a sulfur-based curing system, or an amine-based curing system.
[0097] The thermoplastic elastomer compositions described herein may comprise a single BIMSM or a mixture of two or more BIMSMs (eg, a dual reactor product or a melt blended composition).
[0098] Nevertheless, the present disclosure may be applicable to any other suitable halogenated isobutylene-p-methyl-styrene terpolymers wherein the halogen atom is, for example, chlorine or fluorine.
[0099] Thermoplastic elastomer compositions as described herein may comprise a single thermoplastic polymer or a mixture of two or more thermoplastic polymers. For example, in some embodiments, the thermoplastic phase comprises a polypropylene homopolymer. In other preferred embodiments, the thermoplastic phase is a blend of a thermoplastic polyolefin and a soft thermoplastic elastomer phase, wherein the soft thermoplastic elastomer phase has a Shore A hardness in the range of 20 to 96, and is 20 to 50 when measured on the Shore D scale, and a tensile strength at break of 2MPa to 20MPa. Preferred thermoplastic polymers and soft thermoplastic elastomer phases that can be used for the present invention are described in detail in subsequent embodiments.
[0100] The thermoplastic phase can be present in the thermoplastic elastomer composition at 10 to 90 phr, or 10 to 50 phr, or 12.5 to 47.5 phr, or 15 to 80 phr, or 15 to 45 phr, or 17.5 to 42.5 phr, 20 to 75 phr, or 20 to 40 phr, 30 to 70 phr, or 35 to 65 phr. The thermoplastic elastomer composition is further described below.
[0101] Any suitable vulcanizing agent can be used. Of particular note are the curing agents described in the 35th row of the 19th column to the 30th row of the 20th column of the 7,915,354 United States Patent, which description is incorporated herein by reference (e.g., sulfur curing agent, resin curing agent, amine curing agent). Resin curing agent, sulfur curing agent or amine curing agent will be able to further adjust the viscoelasticity of the thermoplastic elastomer composition and improve material strength. Curing aids (e.g., zinc dimethacrylate (ZDMA)) or those described in the description that have been incorporated into the 7,915,354 United States Patent can also be included. For pharmaceutical applications, amine curing agents are preferred.
[0102] The phenolic resin-based curing system of the thermoplastic elastomer composition comprises a curing agent comprising one or more of the following: 0.1 phr to 20 phr of stannous chloride; 0.1 phr to 15 phr of a metal oxide; 0.05 phr to 10 phr of stearic acid; and 0.5 phr to 20 phr of a phenolic resin. The phenolic resin may be present in the thermoplastic elastomer composition at 0.5 phr to 20 phr, 1 phr to 15 phr, 1.5 phr to 10 phr, or 2 phr to 5 phr. The phenolic resin-based curing system is further described below. Examples of curing agents include, but are not limited to, phenolic resins suitable for reacting with halogen donor active agents. Other examples include phenolic resin curing agents (e.g., described in U.S. Pat. No. 5,750,625, also incorporated herein by reference). The phenolic resin may be selected from any suitable alkylphenol resin, such as octylphenol resin (e.g., SP-1044; SP-1045; HRJ-10518; SP-1055; SP-1056; RIBETAK R-7530).
[0103] The sulfur cure system of the thermoplastic elastomer composition comprises a sulfur curing agent comprising one or more of: 0.1 to 10 phr of MBTS; 0.01 to 5 phr of sulfur; 0.1 to 10 phr of metal oxide; and 0.5 to 15 phr of stearic acid.
[0104] Preferably, the amine curing system of the thermoplastic elastomer composition for pharmaceutical applications comprises one or more amine curing agents present in an amount of 0.1 to 10 phr. The one or more amine curing agents include, but are not limited to, (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
[0105] The reinforcing filler can be present in the thermoplastic elastomer composition at 1 phr to 30 phr, 2 phr to 25 phr, 5 phr to 20 phr or 10 phr to 15 phr. The reinforcing filler is further described below. Examples of reinforcing fillers include, but are not limited to, mineral reinforcing fillers (talc, calcium carbonate, clay, silica, aluminum trihydrate, etc.). For example, clay can be present in the thermoplastic elastomer composition so that a specific component (such as stannous chloride powder) is delivered to a desired location during reactive extrusion. The reinforcing filler can be added as a single batch or as multiple mixed batches at different times during the blending process.
[0106] Before and / or after the curing process, the processing oil may be present in the thermoplastic elastomer composition at 10 to 100 phr, 15 to 75 phr, or 20 to 50 phr. Before the curing process, the processing oil may be present in the thermoplastic elastomer composition at 10 to 100 phr, 15 to 75 phr, 20 to 50 phr, 20 to 80 phr, 30 to 70 phr, or 40 to 60 phr. After the curing process, the processing oil may be present in the thermoplastic elastomer composition at 10 to 100 phr, 15 to 75 phr, 20 to 50 phr, 10 to 30 phr, or 15 to 25 phr.
[0107] The process oil may be an oil comprising a polyisobutylene (PIB) polymer (any suitable example of a PIB polymer, as it is compatible with BIMSM (e.g., with EXXPRO TM The polymer is used as a processing aid due to its miscibility and its acceptance in pharmaceutical applications where other oils and plasticizers are not normally permitted. Examples of PIBs may include INDOPOL TMH100 (available from INEOS Oligomers USA LLC, League City, Texas). Preferred PIB polymers have a specific gravity of 0.75 to 1; a kinematic viscosity (Kv) at 100°C of 100 ) is 50mm 2 / s to 3000mm 2 / s (50cSt to 3000cSt), or 60mm 2 / s to 2900mm 2 / s (70cSt to 2700cSt), or 70mm 2 / s to 2800mm 2 / s (70cSt to 2700cSt).
[0108] INDOPOL TM Typical characteristics of H100 are as follows:
[0109]
[0110] The thermoplastic elastomer composition described herein may further include additives, which may include but are not limited to curing agents, cross-linking agents, plasticizers, compatibilizers, etc., and any combination thereof.
[0111] The metal oxide compound may be present in the thermoplastic elastomer composition. In at least one embodiment, the metal oxide is selected from magnesium oxide (MgO), zinc oxide (ZnO), manganese oxide (MnO), sodium oxide (Na2O), iron oxide (Fe2O3), silicon dioxide (SiO2), calcium oxide (CaO), aluminum oxide (Al2O3) or mixtures thereof.
[0112] Suitable vulcanization activators include zinc oxide (also referred to as "ZnO"), stearic acid, and the like. These activators can be mixed in an amount ranging from 0.1 phr to 50 phr. Different vulcanization activators can be present in different amounts. For example, in the case where the vulcanization activator includes zinc oxide, the amount of zinc oxide present can be 0 phr to 20 phr, such as 0 phr to 10 phr, such as 0 phr to 5 phr, such as 0 phr to 2 phr, and the amount of stearic acid used can preferably be in the range of 0.05 phr to 15 phr, such as 0.1 phr to 10 phr, such as about 1 phr.
[0113] Other additives may be selected from any known additives useful in thermoplastic elastomer compositions, and include in particular one or more of the following:
[0114] Vulcanization accelerator: The composition of the present disclosure may contain 0.1 to 15 phr, 1 to 10 phr, or 2 to 5 phr of a vulcanization accelerator, examples of which include thiazoles (e.g., 2-mercaptobenzothiazole or mercaptobenzothiazole disulfide (MBTS)); guanidines (e.g., diphenylguanidine); sulfenamides (e.g., N-cyclohexylbenzothiazolesulfenamide); dithiocarbamates (e.g., zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc dibenzyldithiocarbamate (ZBEC); and zinc dibutyldithiocarbamate); thioureas (e.g., 1,3-diethylthiourea), thiophosphates, and the like;
[0115] Processing aids (e.g., polyethylene glycol);
[0116] Sponge-grade or foam-grade additives, such as blowing agents or foaming agents, where foaming may be desired, particularly in embodiments where the Mooney viscosity is very high, such as those suitable for use in sponge-grade embodiments. Examples of such agents include: azodicarbonamide (ADC), o-benzenesulfonylhydrazide (OBSH), p-toluenesulfonylhydrazide (TSH), 5-phenyltetrazole (5-PT), and sodium bicarbonate in citric acid. Microcapsules may also or alternatively be used for such foaming applications. These may include heat-expandable microspheres comprising a polymer shell wherein the propellant is contained within the polymer shell. Suitable examples are described in U.S. Pat. Nos. 6,582,633 and 3,615,972, WIPO Publication Nos. WO 99 / 46320 and WO 99 / 43758, the contents of which are incorporated herein by reference. Examples of such heat-expandable microspheres include EXPANCEL available from Akzo Nobel NV. TM products, and ADVANCELL available from Sekisui TM In other embodiments, sponging or foaming can be achieved by injecting gas and / or liquid (e.g., water, CO2, N2) directly into the rubber in the extruder for foaming after the composition passes through the die; and
[0117] Various other additives may also be included, such as antioxidants (e.g., 1,2-dihydro-2,2,4-trimethylquinoline; 6PPD), wax antiozonants (e.g. 4756A), stabilizers, preservatives, UV absorbers, antistatic agents, slip agents, hygroscopic agents (e.g., calcium oxide), pigments, dyes or other colorants.
[0118] The thermoplastic elastomer composition of the present disclosure can be formed by combining a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and additional additives as needed using any suitable method known in the field of polymer processing. For example, a thermoplastic elastomer composition can be prepared by blending a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and additional additives as needed in a molten state. The components of the blend can be blended in any order. For example, the blending process can be an in-situ blending process carried out in any reactor suitable for the process. Therefore, blending can be, for example, twin screw extrusion (TSE) blending or batch mixing (e.g., BANBURY TM ).
[0119] In at least one example, a method for preparing a thermoplastic elastomer composition of PPH and BIMSM includes contacting a Ziegler-Natta catalyst with a propylene monomer in a first reactor to form a PPH polymer as described herein. For the purposes of this disclosure, any commercially available PPH may be used. The method also includes preparing a BIMSM (commercially available or formed in situ by using any method suitable for BIMSM production). The method may include transferring the PPH to a second reactor, or transferring the BIMSM to a first reactor, and recovering a mixture of the PPH and BIMSM from the second reactor or the first reactor, respectively. The recovered thermoplastic elastomer composition may then be crosslinked, for example, as described in more detail below.
[0120] The blend can be prepared by combining the thermoplastic phase and the BIMSM, for example, in a twin-screw extruder.
[0121] In another embodiment, the method of blending the rubber polymer comprising the thermoplastic phase and the BIMSM can be in a batch mixer (such as a BANBURY TM or BARBENDER TM The polymers may be melt blended in an extruder (e.g., a mixer). Blending may include melt blending the thermoplastic phase and the BIMSM in an extruder (e.g., a single screw extruder or a twin screw extruder). Suitable examples of extrusion techniques for polymer blends may be described in more detail in Plastics Extrusion Technology, F. Hensen, ed. (Hanser, 1988), pp. 26-37, and Handbook of Polypropylene, EP Moore, Jr., ed. (Hanser, 1996), pp. 304-348.
[0122] The thermoplastic phase and BIMSM may also be blended by a combination of methods including, but not limited to, solution blending, melt mixing, compounding in a shear mixer, and combinations thereof. For example, dry blending followed by melt blending in an extruder, or batch mixing of some components followed by melt blending with other components in an extruder. The thermoplastic phase and BIMSM may also be blended using a double cone blender, a ribbon blender, or other suitable blender, or in a FARREL CONTINUOUS MIXER. TM (FCM TM ) are blended.
[0123] Thermoplastic phase, BIMSM, curing agent, processing oil and optional additional additives (eg, reinforcing fillers, crosslinking agents (or crosslinking aids), plasticizers, compatibilizers, etc.) can be blended in different orders, which in some cases can change the properties of the resulting composition.
[0124] For example, a masterbatch containing a thermoplastic phase and a BIMSM and additives (except a curing agent and a crosslinking agent) can be produced at a first temperature. Then, a curing agent and / or a crosslinking agent can be mixed into the masterbatch at a second temperature lower than the first temperature.
[0125] In another embodiment, the masterbatch can be produced by mixing the thermoplastic phase and the BIMSM and additives (except the curing agent and the cross-linking agent) together in one step until the additives are incorporated (e.g., to produce a uniform blend). This is referred to herein as a first pass method or first pass blending. After the first pass blending produces the masterbatch, the curing agent and / or the cross-linking agent can be mixed into the masterbatch to produce the final blend.
[0126] In yet another embodiment, a two-step mixing process can be used to produce a masterbatch. For example, a masterbatch can be produced by mixing the BIMSM with additives (except for curing agents and crosslinking agents) until the additives are incorporated into the BIMSM (e.g., to produce a uniform blend), and then mixing the resulting blend with a thermoplastic phase and curing agents and / or crosslinking agents. This is referred to herein as a second pass method or second pass blending. Alternatively, in the two pass method, a curing agent and / or crosslinking agent can be mixed into the masterbatch after the BIMSM is added to produce the final blend.
[0127] In some double blending, the mixing of the BIMSM / additive (except the curing agent and the cross-linking agent) blend with the thermoplastic phase can be completed in a mixer or other suitable system without removing the BIMSM / additive blend from the mixer (i.e., one-time blending) to produce a masterbatch. Alternatively, the BIMSM / additive (except the curing agent and the cross-linking agent) blend can be removed from the mixer or other suitable system for producing the blend and then mixed with the thermoplastic phase in a mixer or other suitable system (i.e., two-time blending) to produce a masterbatch.
[0128] For example, a method for preparing a thermoplastic elastomer composition of a thermoplastic phase, a BIMSM and one or more reinforcing fillers comprises mixing one or more reinforcing fillers through at least two mixing stages. For example, when the reinforcing filler is a mineral filler (e.g., clay), the thermoplastic elastomer composition filled with clay can undergo two mixing stages.
[0129] In embodiments where a curing agent (e.g., a crosslinking agent or a vulcanizing agent) is present in the thermoplastic elastomer composition, the thermoplastic phase of the thermoplastic elastomer composition and the BIMSM may be present in at least partially crosslinked form (i.e., at least a portion of the polymer chains are crosslinked to each other, e.g., as a result of a curing process). Thus, particular embodiments provide an at least partially crosslinked rubber composition prepared by mixing (according to any of the methods described above for polymer blends) a thermoplastic elastomer composition comprising: (a) a BIMSM; (b) a thermoplastic phase (10 to 50 phr); (c) a reinforcing filler; (d) a vulcanization activator, a vulcanizing agent and / or a crosslinking agent; and optionally (e) additional additives.
[0130] The thermoplastic elastomer composition described herein (e.g., comprising a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and optional additional additives) may have a specific gravity of 0.8 g / cm at about 23°C. 3 Up to 1g / cm 3 , or 0.85g / cm 3 Up to 1g / cm 3 , 0.90g / cm 3 Up to 0.98g / cm 3 、0.92g / cm 3 Up to 0.98g / cm 3 .
[0131] The thermoplastic elastomer compositions described herein (e.g., comprising a thermoplastic phase, BIMSM, curative, processing oil, and optional additional additives) may have water vapor (%) of 0.01% to 0.03%, 0.012% to 0.028%, 0.014% to 0.026%, or 0.020% to 0.026%.
[0132] The thermoplastic elastomer composition described herein (eg, comprising a thermoplastic phase, BIMSM, curative, processing oil, and optional additional additives) may have an extruded surface Ra (μm) of 140 to 190 μm, 145 to 180 μm, or 150 to 170 μm.
[0133] The thermoplastic elastomer composition described herein (eg, comprising a thermoplastic phase, a BIMSM, a curative, a processing oil, and optional additional additives) may have a tensile strength (MPa) of 1 MPa to 10 MPa, 2 MPa to 8 MPa, or 4 MPa to 6 MPa.
[0134] The thermoplastic elastomer composition described herein (eg, comprising a thermoplastic phase, a BIMSM, a curative, a processing oil, and optional additional additives) may have a 100% modulus (MPa) of 1 to 5 MPa, 1.2 to 4.8 MPa, 1.4 to 4.6 MPa, or 1.6 to 4.4 MPa.
[0135] The thermoplastic elastomer composition described herein (e.g., comprising a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and optional additional additives) may have an elongation at break (%) of 100% to 500%, or 120% to 450%, or 140% to 425%, or 160% to 400%.
[0136] The permeability (cc.mm / m 2 ·day·mmHg) can be 0.1cc·mm / m 2 ·day·mmHg to 1cc·mm / m 2 ·day·mmHg, or 0.2cc·mm / m 2 ·day·mmHg to 0.8cc·mm / m 2 ·day·mmHg, or 0.4cc·mm / m 2 ·day·mmHg to 0.6cc·mm / m 2 ·day·mmHg.
[0137] The thermoplastic elastomer composition described herein (eg, comprising a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and optional additional additives) may have a punch force (maximum force (N) in 10 punctures) of 1 to 10.
[0138] The thermoplastic elastomer composition described herein (eg, comprising a thermoplastic phase, a BIMSM, a curing agent, a processing oil, and optional additional additives) may have a fragmentation capacity (number of fragmented particles in 48 punctures of 12 vials) of 1 to 15.
[0139] The thermoplastic elastomer compositions described herein (e.g., comprising a thermoplastic phase, BIMSM, curative, processing oil, and optional additional additives) may have a hardness (Shore A) of 40 to 90, 42 to 80, or 44 to 70, or 30 to 60, 35 to 55, or 40 to 50.
[0140] Brominated isobutylene p-methylstyrene terpolymer
[0141] The thermoplastic elastomer compositions described herein comprise one or more BIMSMs.
[0142] The BIMSM of the present disclosure may have a Mooney viscosity (ML 1+8, 125° C.) of 30 MU to 50 MU according to the ASTM D1646 test method.
[0143] The BIMSM of the present disclosure may have a benzyl bromide content of 0.3 mol % to 5 mol %, or 0.5 mol % to 4.5 mol %, or 1 mol % to 4 mol %, or 1.5 mol % to 3.5 mol %.
[0144] The BIMSM of the present disclosure may have a calcium content of 0.01 wt % to 0.5 wt %, or 0.02 wt % to 0.25 wt %, or 0.03 wt % to 0.20 wt %, or 0.04 wt % to 0.15 wt %, based on the total weight percentage of the BIMSM.
[0145] The BIMSM of the present disclosure may have a water content of 0.01 wt % to 0.5 wt %, or 0.02 wt % to 0.4 wt %, or 0.03 wt % to 0.3 wt %, based on the total weight percentage of the BIMSM.
[0146] The BIMSM may be used as a solution polymerized BIMSM or as an emulsion polymerized BIMSM when produced by solution polymerization or emulsion polymerization, respectively.
[0147] Suitable examples of BIMSM could include EXXPRO TM 3745、EXXPRO TM 3433、EXXPRO TM 3563 and EXXPRO TM 3035(All EXXPRO TMBrominated isobutylene-p-methylstyrene terpolymers are all made by ExxonMobil Chemical, Baytown, Texas). For example, EXXPRO TM 3745 can be used in thermoplastic elastomer compositions and EXXPRO TM 3745: Mooney viscosity (ML 1+8, 125°C) according to ASTM D1646 test method is 40MU to 50MU; benzyl bromide content is 1.1 mol% to 1.3 mol% and calcium content is 0.07wt% to 0.11wt% based on the total weight percentage of BIMSM; and water content is 0.3wt% based on the total weight percentage of BIMSM.
[0148] In some embodiments, when the butyl rubber includes an isobutylene para-methyl-styrene copolymer, the copolymer may contain a para-methyl-styrene content of about 0.5 wt % to about 25 wt %, or about 2 wt % to about 20 wt %, based on the total weight of the copolymer, with the remainder being isobutylene.
[0149] The thermoplastic elastomer compositions described herein may comprise a single BIMSM or a mixture of two or more BIMSMs, and the BIMSMs may be used in combination with any type of synthetic elastomer other than the BIMSM, and indeed may even be used in combination with polymers other than elastomers (eg, thermoplastic polymers).
[0150] Thermoplastic Polyolefin
[0151] In thermoplastic elastomer composition of the present invention, thermoplastic polyolefin comprises thermoplastic polymer based on propylene, thermoplastic polymer based on ethylene or other suitable thermoplastic polymer based on polyolefin.This main component based on polymer based on propylene, polymer based on ethylene or other suitable polymer based on polyolefin can be homopolymer, random copolymer, impact copolymer or its combination.In some embodiments, the thermoplastic matrix of thermoplastic elastomer composition is the blend of two different thermoplastic polyolefins (for example, polypropylene and polyethylene).In some embodiments, the thermoplastic polyolefin matrix of thermoplastic elastomer composition is the blend of thermoplastic polyolefin and soft thermoplastic elastomer (for example, polypropylene and polyethylene).The subsequent embodiment details the different components used in the thermoplastic phase.
[0152] 1. Propylene-based polymers
[0153] Propylene-based polymers include those solid, generally high molecular weight plastic resins that primarily contain units derived from the polymerization of propylene. At least 75% in some embodiments, at least 90% in other embodiments, at least 95% in other embodiments, and at least 97% of the units of the propylene-based polymers may be derived from the polymerization of propylene. In specific embodiments, these polymers include homopolymers of propylene. Homopolymer polypropylene may include linear chains and / or chains with long chain branches.
[0154] In some embodiments, the propylene-based polymer may include units derived from the polymerization of ethylene and / or α-olefins (such as 1-butene, 1-hexene, 1-octene, 2-methyl-1-propylene, 3-methyl-1-pentene, 4-methyl-1-pentene, 5-methyl-1-hexene, and mixtures thereof. Specifically, it includes reactants, impact copolymers, and random copolymers of propylene and ethylene or higher α-olefins (such as C4-C40 α-olefins, such as C5-C20 α-olefins, such as C6-C10 α-olefins).
[0155] In some embodiments, the propylene-based polymer may include one or more of the following features:
[0156] Propylene-based polymers may include semi-crystalline polymers. In some embodiments, these polymers may be characterized by a crystallinity of at least about 25 wt% or greater, such as about 55 wt% or greater, such as about 65 wt% or greater, such as about 70 wt% or greater. The crystallinity may be determined by dividing the heat of fusion (Hf) of the sample by the heat of fusion of a 100% crystalline polymer, assuming a heat of fusion of 209 joules / gram for polypropylene.
[0157] The propylene-based polymer can have a heat of fusion as measured by ASTM D3418 of about 52.3 J / g or greater, such as about 100 J / g or greater, such as about 125 J / g or greater, such as about 140 J / g or greater.
[0158] The propylene-based polymer can have a weight average molecular weight (Mw) of about 50,000 g / mol to about 2,000,000 g / mol, such as about 100,000 g / mol to about 1,000,000 g / mol, such as about 100,000 g / mol to about 600,000 g / mol, or about 400,000 g / mol to about 800,000 g / mol as measured by GPC with polystyrene standards.
[0159] The propylene-based polymer may have a number average molecular weight (Mn) of about 25,000 g / mol to about 1,000,000 g / mol, such as about 50,000 g / mol to about 300,000 g / mol, as measured by GPC with polystyrene standards.
[0160] The propylene-based polymer may have a g'vis of about 1 or less, such as about 0.9 or less, such as about 0.8 or less, such as about 0.6 or less, such as about 0.5 or less, as measured by the GPC procedure described below.
[0161] The propylene-based polymer may have a melt flow rate (MFR) (ASTM D1238, 2.16 kg weight @ 230°C) of about 0.1 g / 10 min or greater, such as about 0.2 g / 10 min or greater, such as about 0.25 g / 10 min or greater. Alternatively, the MFR may be about 0.1 g / 10 min to about 1500 g / 10 min, such as about 0.5 g / 10 min to about 1000 g / 10 min, such as about 0.5 g / 10 min to about 900 g / 10 min.
[0162] The propylene-based polymer may have a melting temperature (Tm) of about 110°C to about 170°C, such as about 140°C to about 168°C, such as about 160°C to about 165°C as measured by ASTM D3418.
[0163] The propylene-based polymer may have a glass transition temperature (Tg) of about -50°C to about 10°C, such as about -30°C to about 5°C, such as about -20°C to about 2°C as measured by ASTM D3418.
[0164] The propylene-based polymer may have a crystallization temperature (Tc) of about 75°C or greater, such as about 95°C or greater, such as about 100°C or greater, such as about 105°C or greater, such as about 105°C to about 130°C as measured by ASTM D3418.
[0165] In some embodiments, the propylene-based polymer may include a homopolymer of isotactic or syndiotactic polypropylene of high crystallinity. The polypropylene may have a density of about 0.89 g / ml to about 0.91 g / ml, with most of the isotactic polypropylene having a density of about 0.90 g / ml to about 0.91 g / ml. In addition, high molecular weight and ultra-high molecular weight polypropylenes with partial melt flow rates may be used. In some embodiments, the polypropylene resin may be characterized by an MFR (ASTM D-1238; 2.16 kg @ 230 ° C) that may be about 10 dg / min or less, such as about 1.0 dg / min or less, such as about 0.5 dg / min or less.
[0166] In some embodiments, the polypropylene comprises homopolymer polypropylene, random copolymer polypropylene, or impact copolymer polypropylene or a combination thereof. In some embodiments, the polypropylene is a high melt strength (HMS) long chain branching (LCB) homopolymer polypropylene.
[0167] Propylene-based polymers may be synthesized using suitable polymerization techniques known in the art, such as conventional Ziegler-Natta type polymerization and catalysis using single site organometallic catalysts, including metallocene catalysts.
[0168] Examples of polypropylenes that can be used in the TPV compositions described herein include random copolymer polypropylenes such as ExxonMobil TM PP9513, Braskem TM F180A (available from Braskem), ExxonMobil TM PP3155E5, ExxonMobil TM PP9122; Homopolymer PP, such as Achieve TM Advanced PP6936G2, ExxonMobil TM PP5341 (available from ExxonMobil); Achieve TM PP6282NE1 (available from ExxonMobil) and / or polypropylene resins with broad molecular weight distribution described in US 9,453,093 and US 9,464,178; and other polypropylene resins described in US20180016414 and US20180051160; Waymax MFX6 (available from Japan Polypropylene Corporation); Borealis Daploy TM WB140 (available from Borealis AG); and Braskem Ampleo 1025MA and BraskemAmpleo 1020GA (available from Braskem Ampleo); impact copolymer polypropylene such as Achieve TM AdvancedPP8285E1, ExxonMobil TM PP8255E1 and ExxonMobil TM PP8244E1; and other suitable polypropylenes.
[0169] In one or more embodiments, the thermoplastic component may include isotactic polypropylene. In some embodiments, the thermoplastic component may include one or more crystalline propylene homopolymers or propylene copolymers having a melting temperature of about 110°C to about 170°C or higher as measured by DSC. Examples of propylene copolymers may include propylene terpolymers, propylene impact copolymers, random polypropylene and mixtures thereof. Exemplary comonomers may have about 2 carbon atoms, or about 4 carbon atoms to about 12 carbon atoms. In some embodiments, the comonomer may be ethylene.
[0170] The term "random polypropylene" as used herein refers broadly to a single phase copolymer of propylene having up to about 9 wt%, such as from about 2 wt% to about 8 wt%, of an alpha-olefin comonomer. Exemplary alpha-olefin comonomers may have from about 2 carbon atoms, or from about 4 carbon atoms to about 12 carbon atoms. In some embodiments, the alpha-olefin comonomer may be ethylene.
[0171] In one or more embodiments, the thermoplastic resin component can be or include a "propylene-based copolymer". A "propylene-based copolymer" includes at least two different types of monomer units, one of which is propylene. Suitable monomer units may include ethylene and higher α-olefins in the range of C4 to C20 (e.g., 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, or mixtures thereof). In some embodiments, ethylene may be copolymerized with propylene so that the propylene-based copolymer includes propylene-derived units (units derived from propylene monomers on the polymer chain) and ethylene-derived units (units derived from ethylene monomers on the polymer chain).
[0172] 2. Polypropylene homopolymer
[0173] The thermoplastic elastomer composition described herein may contain: 10 to 50 phr (or 12.5 to 47.5 phr, or 15 to 45 phr, or 17.5 to 42.5 phr, or 20 to 40 phr) of PPH, and its melt flow rate (MFR) (230°C / 2.16 kg) is 0.2 to 2000 g / 10 min (or 0.5 to 1500 g / 10 min, or 0.5 to 1000 g / 10 min, or 0.5 to 500 g / 10 min, or 0.5 to 100 g / 10 min, more preferably 0.5 to 20 g / 10 min) based on ASTM D1238 test method.
[0174] The thermoplastic elastomer compositions described herein may comprise a single PPH or a mixture of two or more PPHs (eg, a dual reactor product or a blended PPH).
[0175] The PPH may be a linear or branched homopolymer of propylene monomer. Alternatively, the polypropylene may be a polypropylene copolymer produced from propylene and one or more comonomers in a pentene to comonomer (cumulative) molar ratio of 1:1 to 500:1 (or 5:1 to 250:1, 1:1 to 100:1, 1:1 to 10:1, 5:1 to 50:1, 50:1 to 250:1, or 100:1 to 500:1). For example, the polypropylene polymer may be a propylene homopolymer or a propylene copolymer, such as propylene-ethylene and / or propylene-α-olefin (preferably C3 to C 20 ) (such as propylene-hexene copolymer or propylene-octene copolymer), whose Mw / Mn is greater than 1 to 4 (preferably greater than 1 to 3).
[0176] The propylene monomer may be contacted with a catalyst system comprising an activator and at least one catalyst compound (such as a metallocene or Ziehl-Natta catalyst compound). The catalyst compound and the activator may be combined in any order and are typically combined prior to contact with the monomer. The catalyst system may comprise an inert support material. Preferably, the support material is a porous support material, such as talc and an inorganic oxide. Other support materials include zeolites, clays, organoclays or any other organic or inorganic support materials, or mixtures thereof.
[0177] Preferably, the support material is an inorganic oxide in finely divided form. Suitable inorganic oxide materials for the catalyst system herein include metal oxides of the 2nd, 4th, 13th and 14th families, such as silica, alumina and mixtures thereof. Other inorganic oxides that can be used alone or in combination with silica or alumina are magnesium oxide, titanium dioxide, zirconium oxide and the like. However, other suitable support materials can be used, for example, finely divided functionalized polyolefins, such as finely divided polypropylene. Particularly useful supports include magnesium oxide, titanium dioxide, zirconium oxide, montmorillonite, phyllosilicates, zeolites, talc, clays and the like. In addition, combinations of these support materials can be used, such as silica-chromium, silica-alumina, silica-titania and the like. Preferred support materials include Al2O3, ZrO2, SiO2 and combinations thereof, more preferably SiO2, Al2O3 or SiO2 / Al2O3.
[0178] It is preferred that the support material (most preferably an inorganic oxide) have a 2 / g to about 700m 2 / g range, a pore volume in the range of about 0.1 cc / g to about 4.0 cc / g, and an average particle size in the range of about 5 μm to about 500 μm. More preferably, the surface area of the support material is about 50 m 2 / g to about 500m 2 / g, a pore volume of about 0.5cc / g to about 3.5cc / g, and an average particle size of about 10μm to about 200μm. Most preferably, the surface area of the support material is about 100m 2 / g to about 400m 2 / g range, the pore volume is about 0.8cc / g to about 3.0cc / g, and the average particle size is about 5μm to about 100μm. The average pore size of the support material used in the present invention is to In the range of to about , most preferably to about In some embodiments, the support material is high surface area amorphous silica (surface area = 300 m 2 / gm; pore volume is 1.65cm 3 / gm). Preferred silica is produced by the Davison Chemical Division of Grace Chemical Company under the trade name Davison TM 952 or Davison TM 955 sales. In other embodiments, DAVISON TM 948.
[0179] The support material should be dry, i.e., free of absorbed water. Drying of the support material can be effected by heating or calcining at about 100°C to about 1000°C, preferably at least about 600°C. When the support material is silica, it is heated to at least 200°C, preferably about 200°C to about 850°C, and most preferably about 600°C; and for a period of about 1 minute to about 100 hours, about 12 hours to about 72 hours, or about 24 hours to about 60 hours. The calcined support material needs to have at least some reactive hydroxyl (OH) groups to produce the supported catalyst system of the present invention. The calcined support material is then contacted with at least one polymerization catalyst comprising at least one catalyst compound and an activator.
[0180] The support material with reactive surface groups (usually hydroxyl groups) is made into a slurry in a non-polar solvent, and the resulting slurry is contacted with a solution of a catalyst compound and an activator. In some embodiments, the slurry of the support material is first contacted with the activator for a period of about 0.5 hour to about 24 hours, about 2 hours to about 16 hours, or about 4 hours to about 8 hours. Then the solution of the catalyst compound is contacted with the carrier / activator separated. In some embodiments, the supported catalyst system is generated in situ. In an alternative embodiment, the slurry of the support material is first contacted with the catalyst compound for a period of about 0.5 hour to about 24 hours, about 2 hours to about 16 hours, or about 4 hours to about 8 hours. Then the slurry of the supported catalyst compound is contacted with the activator solution.
[0181] The mixture of catalyst, activator and support is heated to about 0° C. to about 70° C., preferably to about 23° C. to about 60° C., preferably at room temperature. The contact time is usually in the range of about 0.5 hours to about 24 hours, about 2 hours to about 16 hours, or about 4 hours to about 8 hours.
[0182] Suitable non-polar solvents are materials in which all reactants (i.e., activators and catalyst compounds) used herein are at least partially soluble and are liquid at the reaction temperature. Preferred non-polar solvents are alkanes (such as isopentane, hexane, n-heptane, octane, nonane, and decane), although a variety of other materials including cycloalkanes (such as cyclohexane), aromatic compounds (such as benzene, toluene, and ethylbenzene) may also be employed.
[0183] The propylene polymer may comprise propylene and optionally a comonomer comprising one or more of ethylene or a C4 to C 40 Olefins (preferably C4 to C 20 Olefins, or preferably C6 to C 12 Olefins). C4 to C 40 The olefin monomers may be linear, branched or cyclic. 40 The cyclic olefins may be strained or unstrained, monocyclic or polycyclic, and may optionally include heteroatoms and / or one or more functional groups.
[0184] The polymerization process for preparing PPH can be implemented in any manner known in the art. Any suspension polymerization process, homogeneous polymerization process, bulk polymerization process, solution polymerization process, slurry polymerization process or gas phase polymerization process known in the art can be used. Such a process can be operated in batch mode, semi-batch mode or continuous mode. Homogeneous polymerization process and slurry process are preferred (homogeneous polymerization process is defined as a process in which at least 90wt% of the product is soluble in the reaction medium). Bulk homogeneous process is particularly preferred (bulk process is defined as a process in which the monomer concentration in all feeds fed to the reactor is 70 volume % or greater). Alternatively, a solvent or diluent is not present in or is not added to the reaction medium (except a small amount of a carrier or other additive used as a catalyst system, or an amount generally found with the monomer; for example, propane in propylene). In another embodiment, the process is a slurry process. As used herein, the term "slurry polymerization process" refers to a polymerization process in which a supported catalyst is used and monomers are polymerized on supported catalyst particles. At least 95 wt% of the polymer product derived from the supported catalyst is in the form of solid particles (not dissolved in the diluent) in granular form.
[0185] Suitable diluents / solvents for the polymerization include non-coordinating inert liquids. Examples include: straight chain and branched hydrocarbons such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof; cyclic and alicyclic hydrocarbons such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane and mixtures thereof, such as the commercially available (Isopar TM fluid); fully halogenated hydrocarbons, such as perfluorinated C 4- C 10 Alkanes, chlorobenzenes; and aromatic substituted and alkyl substituted aromatic compounds, such as benzene, toluene, mesitylene and xylene. Suitable solvents also include liquid olefins that can be used as monomers or comonomers, including ethylene, propylene, 1-butene, 1-hexene, 1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-octene, 1-decene and mixtures thereof. In a preferred embodiment, aliphatic hydrocarbon solvents can be used as solvents, such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof; cyclic hydrocarbons and alicyclic hydrocarbons, such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane and mixtures thereof. In another embodiment, the solvent is not aromatic, and preferably the amount of aromatic compounds present in the solvent is less than 1 wt%, preferably less than 0.5 wt%, preferably less than 0 wt%, based on the weight of the solvent.
[0186] In at least one embodiment, the feed concentration of monomers and comonomers for the polymerization is 60 vol% solvent or less, preferably 40 vol% or less, or preferably 20 vol% or less based on the total volume of the feed stream. Preferably, the polymerization is run as a bulk process.
[0187] Preferred polymerizations can be run at any temperature and / or pressure suitable for obtaining the desired propylene polymer. Typical temperatures and / or pressures include: temperatures in the range of about 0°C to about 300°C, preferably about 20°C to about 200°C, preferably about 35°C to about 150°C, preferably about 40°C to about 120°C, preferably about 45°C to about 80°C; and pressures in the range of about 0.35MPa to about 10MPa, preferably about 0.45MPa to about 6MPa, or preferably about 0.5MPa to about 4MPa.
[0188] In a typical polymerization, the reaction run time is up to 300 minutes, preferably in the range of about 5 minutes to 250 minutes, or preferably about 10 minutes to 120 minutes.
[0189] Hydrogen may be present in the polymerization reactor at a partial pressure of 0.001 psig to 50 psig (0.007 kPa to 345 kPa), preferably 0.01 psig to 25 psig (0.07 kPa to 172 kPa), more preferably 0.1 psig to 10 psig (0.7 kPa to 70 kPa).
[0190] Little or no alumoxane may be used in the process of producing the polymer. Preferably, the alumoxane may be present at 0 mol%, or the alumoxane may be present at a molar ratio of aluminum to transition metal of less than 500:1, preferably less than 300:1, preferably less than 100:1, preferably less than 1:1.
[0191] In addition, little or no scavenger may be used in the process of producing the propylene polymer. Preferably, the scavenger (such as trialkylaluminum) may be present at 0 mol%, or the scavenger may be present at a molar ratio of scavenger metal to transition metal of less than 100:1, preferably less than 50:1, preferably less than 15:1, preferably less than 10:1.
[0192] In at least one embodiment, the polymerization is: 1) carried out at a temperature of 0°C to 300°C (preferably 25°C to 150°C, preferably 40°C to 120°C, preferably 45°C to 80°C); 2) carried out at a pressure of atmospheric pressure to 10MPa (preferably 0.35MPa to 10MPa, preferably 0.45MPa to 6MPa, preferably 0.5MPa to 4MPa); 3) carried out in an aliphatic hydrocarbon solvent (such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof); cyclic hydrocarbons and alicyclic hydrocarbons (such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane, and mixtures thereof); preferably, the aromatic compound is preferably present in the solvent at less than 1 wt%, preferably less than 0.5 wt%, preferably 0 wt% based on the weight of the solvent; 4) wherein the catalyst system for polymerization comprises less than 0.5 mol%, preferably 0 mol% of aluminoxane, or the aluminoxane is present in a molar ratio of aluminum to transition metal of less than 500:1, preferably less than 300:1, preferably less than 100:1, preferably less than 1:1 ; 5) the polymerization preferably occurs in one reaction zone; 6) the productivity of the catalyst compound is at least 80,000 g / mmol / hr (preferably at least 150,000 g / mmol / hr, preferably at least 200,000 g / mmol / hr, preferably at least 250,000 g / mmol / hr, preferably at least 300,000 g / mmol / hr); 7) optionally, there is no scavenger (such as a trialkylaluminum compound) (e.g., present at 0 mol%, or the scavenger is present at a small amount); 1, preferably less than 50:1, preferably less than 15:1, preferably less than 10:1 molar ratio of scavenger metal to transition metal); and 8) optionally, the partial pressure of hydrogen present in the polymerization reactor is 0.001 psig to 50 psig (0.007 kPa to 345 kPa) (preferably 0.01 psig to 25 psig (0.07 kPa to 172 kPa), more preferably 0.1 psig to 10 psig (0.7 kPa to 70 kPa)). In a preferred embodiment, the catalyst system used in the polymerization comprises no more than one catalyst compound. A "reaction zone", also known as a "polymerization zone", is a container in which polymerization occurs, such as a batch reactor. When multiple reactors are used in a series configuration or a parallel configuration, each reactor is considered to be a separate polymerization zone. For multi-stage polymerization in batch reactors and continuous reactors, each polymerization stage is considered to be a separate polymerization zone. In a preferred embodiment, polymerization occurs in one reaction zone. Unless otherwise stated, room temperature is 23°C.
[0193] Other additives as needed may also be used in the polymerization, such as one or more scavengers, promoters, modifiers, reducing agents, oxidants, hydrogen, alkyl aluminum, silane or chain transfer agents (such as alkyl aluminoxane, a compound represented by the formula AlR3 or ZnR2 (wherein each R is independently a C1 to C8 aliphatic group, preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl or its isomers) or a combination thereof, such as diethyl zinc, methyl aluminoxane, trimethyl aluminum, triisobutyl aluminum, trioctylaluminum or a combination thereof).
[0194] The melt flow rate (MFR) (230°C / 2.16kg) of the PPH of the present disclosure can be 0.2 g / 10 min to 2000 g / 10 min (or 0.5 g / 10 min to 1500 g / 10 min, or 0.5 g / 10 min to 1000 g / 10 min, or 0.5 g / 10 min to 500 g / 10 min, or 0.5 g / 10 min to 100 g / 10 min, more preferably 0.5 g / 10 min to 20 g / 10 min) based on ASTM D1238 test method.
[0195] 3. Ethylene-based thermoplastic polymers
[0196] Ethylene-based thermoplastic polymers include those solid, high molecular weight plastic resins that primarily comprise units derived from ethylene polymerization. At least 90% in some embodiments, at least 95% in other embodiments, and at least 99% of the units of ethylene-based polymers are derived from ethylene polymerization. In specific embodiments, these polymers include homopolymers of ethylene.
[0197] In some embodiments, the ethylene-based polymer may also include units derived from the polymerization of α-olefins such as propylene, 1-butene, 1-hexene, 1-octene, 2-methyl-1-propylene, 3-methyl-1-pentene, 4-methyl-1-pentene, 5-methyl-1-hexene, and mixtures thereof.
[0198] In some embodiments, the ethylene-based polymer includes one, more, or all of the following features:
[0199] 1) a melt index (MI) (ASTM D-1238, 2.16 kg @ 190°C) of about 0.1 dg / min to about 1,000 dg / min, such as about 1.0 dg / min to about 200 dg / min or about 7.0 dg / min to about 20.0 dg / min.
[0200] 2) a melting temperature (Tm) of about 140°C to about 90°C, such as about 135°C to about 125°C, or about 130°C to about 120°C.
[0201] 3) Density greater than 0.90 g / cm3.
[0202] Ethylene-based polymers can be synthesized using suitable polymerization techniques known in the art, such as conventional Ziegler-Natta type polymerizations and catalysis using single-site organometallic catalysts, including metallocene catalysts. Ethylene-based polymers are commercially available. For example, polyethylene is available under the trade name ExxonMobil TM Polyethylene is commercially available from ExxonMobil of Houston, Texas. Ethylene-based copolymers are sold under the trade name ExxonMobil TM Polyethylene is commercially available (from ExxonMobil of Houston, Texas) and includes metallocene-produced linear low-density polyethylene, including Exceed TM 、Enable TM and Exceed TM XP. Examples of ethylene-based thermoplastic polymers useful in certain embodiments of the inventive TPV compositions described herein include ExxonMobil HD7800P, ExxonMobil HD6706.17, ExxonMobil HD7960.13, ExxonMobil HD9830, ExxonMobil AD60-007, Exceed XP 8318ML, Exceed TM XP 6056ML,Exceed 1018HA,Enable TM 2010 Series, Enable TM 2305 Series and ExxonMobil TM LLDPE LL (e.g., 1001, 1002YB, 3003 series), all available from ExxonMobil in Houston, Texas. Other examples of ethylene-based thermoplastic polymers useful in certain embodiments of the inventive TPV compositions described herein include Innate TM ST50 and Dowlex TM , which is available from The Dow Chemical Company, Midland, Michigan.
[0203] In some embodiments, the PE can be any crystalline PE, preferably a high density PE ("HDPE") having a density (sp. gr.) of about 0.940 g / cc to about 0.965 g / cc and a MI in the range of 0.1 to 20. HDPE is commercially available in different forms, each with a relatively high polydispersity index (Mw / Mn) in the range of about 20 to about 40. In some embodiments, the PE is a bimodal high density PE, such as ExxonMobil HD 7800P, which is a high density polyethylene having a melt flow index of 0.25 g / 10 min. ExxonMobil HD 7800P is available from ExxonMobil in Houston, Texas.
[0204] In one or more embodiments, the thermoplastic phase comprises a polyethylene resin. In one or more embodiments, the polyethylene resin is a polyethylene homopolymer. In one or more embodiments, the polyethylene may be characterized by a weight average molecular weight of about 100 to 250 kg / mole, or about 110 to 220 kg / mole, or about 150 to 200 kg / mole. The polyethylene may be characterized by a polydispersity index (Mw / Mn) of less than 12, or less than 11, or less than 10, or less than 9.
[0205] PE can be present in the thermoplastic vulcanizate rubber composition as a blend with PP (such as isotactic polypropylene) in an amount greater than 5wt%, or greater than 7wt%, or greater than 10wt% based on the weight of the thermoplastic vulcanizate rubber composition. If PE is present as a blending component with PP (such as isotactic polypropylene), the amount of PE in the thermoplastic vulcanizate rubber composition can be 5wt% to 25wt%.
[0206] Soft thermoplastic elastomer
[0207] In some preferred embodiments, the thermoplastic phase may include a blend of the above-mentioned thermoplastic polyolefin and a soft thermoplastic elastomer, with a blend ratio of 5wt% to 80wt% of the thermoplastic polyolefin and 95wt% to 20wt% of the soft thermoplastic elastomer. In some embodiments, the Shore A hardness of the soft thermoplastic elastomer is in the range of 20 to 96, and is 20 to 50 when measured on the Shore D scale, and the tensile strength at break is 2MPa to 20MPa. The present disclosure further illustrates a thermoplastic vulcanizate rubber composition, wherein the soft thermoplastic elastomer is preferably an olefin-based block copolymer, the olefin-based block copolymer comprising a crystallizable ethylene-octene block alternating with a low crystallinity ethylene-octene block, the crystallizable ethylene-octene block having an alpha-olefin comonomer content of less than 10wt% and a melting point greater than 90°C, the low crystallinity ethylene-octene block having a comonomer content greater than 10wt% and a melting point less than 90°C. The disclosure further shows a thermoplastic vulcanizate rubber composition, wherein the soft thermoplastic elastomer is preferably an olefin-based block copolymer blend, and the olefin-based block copolymer blend includes ethylene-propylene (EP) copolymer, isotactic polypropylene (iPP) and EP-iPP diblock polymer. The disclosure further shows a thermoplastic vulcanizate rubber composition, except that it includes a polypropylene homopolymer or as a substitute for a polypropylene homopolymer, it preferably includes styrene-isobutylene styrene (SIBS). Styrene-isobutylene styrene polymers can also be used to replace polybutene oil. The disclosure further shows a thermoplastic vulcanizate rubber composition, which includes a propylene-based elastomer as a thermoplastic elastomer or for replacing polybutene oil, and the propylene-based elastomer includes a unit derived from a propylene main part and about 5wt% to about 25wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins. The present disclosure further shows a thermoplastic vulcanizate composition comprising an olefin-based polymer composed of 50 wt % to 100 wt % of structural units derived from 4-methyl-1-pentene, and 0 wt % to 50 wt % of structural units derived from at least one olefin selected from olefins other than 4-methyl-1-pentene having 2 to 20 carbon atoms.
[0208] The following embodiments describe different soft thermoplastic elastomers that can be used in the present disclosure.
[0209] 1. Ethylene / α-olefin multi-block copolymer
[0210] The term "ethylene / α-olefin multi-block copolymer" is a copolymer comprising blocks or segments derived from ethylene and one or more copolymerizable α-olefin comonomers in polymerized form. Block copolymers are characterized by multiple blocks or segments of two or more polymerized monomer units, resulting in blocks that are different based on chemical composition or physical properties. The term "ethylene / α-olefin multi-block copolymer" includes block copolymers having two blocks (diblocks) and more than two blocks (multiblocks). Preferably, the ethylene / α-olefin multi-block copolymer comprises crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, the crystallizable ethylene-octene blocks having an α-olefin comonomer content of less than 10wt% and a melting point of greater than 90°C, and the low crystallinity ethylene-octene blocks having a comonomer content of greater than 10wt% and a melting point of less than 90°C. Preferably, the ethylene / α-olefin multi-block copolymer comprises ethylene units of the majority molar portion (i.e., ethylene accounts for at least greater than 50 mole percent of the polymer). More preferably, ethylene comprises at least 60 mole percent, at least 70 mole percent, or at least 80 mole percent, with the remainder of the polymer comprising at least one other comonomer (which is preferably an alpha-olefin having 3 or more carbon atoms, or 4 or more carbon atoms). For many ethylene / octene multi-block copolymers, the composition comprises an ethylene content greater than 80 mole percent of the total polymer and an octene content of 10 to 15 mole percent, or 15 to 20 mole percent of the total polymer.
[0211] Suitable monomers for preparing the ethylene / α-olefin multi-block copolymer of the present invention include ethylene and one or more addition polymerizable monomers other than ethylene. Examples of suitable comonomers include linear or branched α-olefins of 3 to 30 carbon atoms, or 3 to 20 carbon atoms, or 4 to 12 carbon atoms, such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene; cycloolefins of 3 to 30 carbon atoms or 3 to 20 carbon atoms, such as cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethyl-1,2,3,4,4a,5,8, 8a-octahydronaphthalene; dienes and polyolefins such as butadiene, isoprene, 4-methyl-1,3-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 1,5-hexadiene, 1,4-hexadiene, 1,3-hexadiene, 1,3-octadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, ethylidene norbornene, vinyl norbornene, dicyclopentadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene and 5,9-dimethyl-1,4,8-decatriene; and 3-phenylpropylene, 4-phenylpropylene, 1,2-difluoroethylene, tetrafluoroethylene and 3,3,3-trifluoro-1-propylene. In an embodiment, the comonomer is selected from butene, hexene and octene. In a preferred embodiment, the comonomer is 1-octene.
[0212] Ethylene / alpha-olefin multi-block copolymers include different amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units comprising a major portion of ethylene (such as greater than 90 weight percent). In some preferred embodiments, hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units wherein the comonomer content (different from the monomer content of ethylene) is greater than the content present in the hard segments. Ethylene / alpha-olefin multi-block copolymers can be produced by a chain shuttling method (such as described in U.S. Patent No. 7,858,706, which is incorporated herein by reference). For example, the method is also described in the following U.S. Patent Nos. 7,608,668, 7,893,166 and 7,947,793.
[0213] In an embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer and has one, more, any combination or all of the following properties:
[0214] (i) a melting temperature (Tm) of 100°C to 130°C, or 105°C to 127°C, or 115°C to 125°C, or 118°C to 122°C, or 125°C;
[0215] (ii) a density of 0.86 g / cc, or 0.87 g / cc, or 0.88 g / cc to 0.89 g / cc;
[0216] (iii) a melt index (MI) of 0.2 g / 10 min to 40 g / 10 min, or 0.5 g / 10 min to 35 g / 10 min, or 0.7 g / 10 min to 30 g / min, or 1 g / 10 min to 10 g / 10 min;
[0217] (vii) a Shore A hardness of 30 to 95, or 40 to 90, or 50 to 80, or 55 to 78, or 60 to 77;
[0218] (viii) Ultimate tensile strength of 1 to 25 MPa, 2 to 20 MPa, 1.5 to 18 MPa, 3 to 17 MPa, 5 to 16 MPa, 6 to 15 MPa.
[0219] (ix) Compression set at 70°C of 20% to 120%, 30% to 100%, 40% to 80%, 45% to 70%.
[0220] In an embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. In an embodiment, the ethylene / octene multi-block copolymer is sold under the trade name INFUSE TM Sold and available from The Dow Chemical Company, Midland, Michigan, USA. In another embodiment, the ethylene / octene multi-block copolymer is INFUSE TM 9100. In an embodiment, the ethylene / octene multi-block copolymer is INFUSE TM 9500. In an embodiment, the ethylene / octene multi-block copolymer is INFUSE TM 9507.
[0221] 2. Propylene-based block copolymer blends
[0222] The term "propylene-based block copolymer blend" refers to a polymer composition comprising a blend of: a) a soft thermoplastic polyolefin copolymer; b) a hard thermoplastic polyolefin; and c) a block copolymer having a soft segment comprising the same units as a) and a hard segment comprising the same units as b). The hard segments of the block copolymer have the same composition as the hard thermoplastic polyolefin in the propylene-based block copolymer blend, and the soft segments of the block copolymer have the same composition as the soft thermoplastic polyolefin copolymer of the propylene-based block copolymer blend. The propylene-based block copolymer blend comprises a hard segment and a hard polymer comprising only or substantially only propylene monomer residues, and a soft segment and a soft polymer comprising only or substantially only ethylene and propylene comonomer residues. When describing a propylene-based block copolymer blend, a "hard" segment refers to a high crystallinity block of a polymerized unit, wherein the comonomer content in the hard segment is less than 5 mol% or less than 2 mol%. In some embodiments, the hard segment comprises all or substantially all propylene units. On the other hand, a "soft" segment refers to an amorphous block, a substantially amorphous block, or an elastomeric block of a polymerized unit having a comonomer content greater than 10 mol%. In some embodiments, the soft segment comprises an ethylene / propylene interpolymer. In addition, the EP-iPP diblock polymer of the propylene-based block copolymer blend comprises 10 wt% to 90 wt% of a hard segment and 90 wt% to 10 wt% of a soft segment. In the soft segment, the weight percentage of ethylene may be in the range of 10% to 75%, or 30% to 70%. In an embodiment, propylene constitutes the remainder of the soft segment. In the hard segment, the weight percentage of propylene may be in the range of 80% to 100%. The hard segment may comprise greater than 90 wt%, 95 wt%, or 98 wt% of propylene. In an embodiment, the propylene-based block copolymer blend comprises a total ethylene content of 15 wt% to 75 wt%, or 20 wt% to 70 wt%, or 25 wt% to 65 wt% based on the total weight of the blend. In an embodiment, the EP-iPP diblock polymer in the propylene-based block copolymer blend has a propylene content of 57 wt% to 52 wt%, or 56.5 wt% to 53 wt%, or 56 wt% to 53 wt%, based on the weight of the EP-iPP diblock polymer.
[0223] The propylene-based block copolymer blends used herein may be prepared by a process comprising contacting an addition polymerizing monomer or mixture of monomers under addition polymerization conditions with a composition comprising at least one addition polymerization catalyst, a cocatalyst, and a chain shuttling agent ("CSA"), the process being characterized by forming at least some of the growing polymer chains under different process conditions in two or more reactors operating under steady state polymerization conditions or in two or more zones of a reactor operating under plug flow polymerization conditions. The propylene-based block copolymer blends described herein may be distinguished from conventional random copolymers, physical blends of polymers, and block copolymers prepared via sequential monomer addition. Propylene-based block copolymer blends can differ from random copolymers in properties such as higher melting temperatures for equivalent amounts of comonomer as described below; from physical blends in properties such as better tensile strength, improved break strength, finer morphology, improved optical properties, and greater impact strength at lower temperatures; and from block copolymers prepared via sequential monomer addition in molecular weight distribution, rheology, shear thinning, rheological ratio, and the presence of block polydispersity.
[0224] The propylene-based block copolymer blend may have a higher melting point than the melting point determined by differential scanning calorimetry. In some embodiments, the highest temperature crystalline melting point (Tm) of the propylene-based block copolymer blend may be greater than 100°C, preferably greater than 120°C, more preferably greater than 125°C. The melt index of the propylene-based block copolymer blend may be in the range of 0.1 g / 10min to 1000 g / 10min, 0.1 g / 10min to 50 g / 10min, 0.1 g / 10min to 30 g / 10min, or 1 g / 10min to 20 g / 10min.
[0225] In some embodiments, the propylene-based block copolymer blends exhibit a Shore A hardness of 30 to 98, or 40 to 95, or 50 to 95, or 60 to 95. In some preferred embodiments, the propylene-based block copolymer blends exhibit a Shore D hardness of 5 to 60, or 10 to 55, or 15 to 50, or 15 to 45. In some embodiments, the propylene-based block copolymer blends exhibit a Vicat softening point of 20° C. to 150° C., or 30° C. to 140° C., or 40° C. to 135° C., or 50° C. to 130° C. Preferably, the propylene-based block copolymer blends exhibit a tensile strength at break of 1.5 MPa to 20 MPa, or 2 MPa to 18 MPa, or 2 MPa to 17 MPa, or 2.5 MPa to 16 MPa. Preferably, the propylene-based block copolymer blend shows a compression set at 70° C. of 40% to 120%, or 50% to 100% MPa, or 55% to 90%, or 60% to 80%. Preferably, the propylene-based block copolymer blend shows an ethylene content of 90 wt% to 15 wt%, or 85 wt% to 20 wt%, 80 wt% to 25 wt%, 77 wt% to 30 wt%.
[0226] Methods that can be used to produce propylene-based block copolymer blends suitable for use in the present invention can be found, for example, in U.S. Patent Application Publication No. 2008 / 0269412 published on October 30, 2008. Suitable catalysts, catalyst precursors, and cocatalysts for use in the present invention include metal complexes, such as those disclosed in WO 2005 / 090426, US 2007 / 0167578, US 2008 / 0311 812, US 2011 / 0082258, U.S. Pat. No. 7,355,089, and WO 2009 / 012215. Propylene-based block copolymer blends themselves are more fully described in U.S. Pat. No. 8,476,366. In an embodiment, the propylene-based block copolymer blend is sold under the trade name INTUNE TM Sold and available from The Dow Chemical Company, Midland, Michigan, USA. In another embodiment, the propylene-based block copolymer blend is INTUNE TM D5545、INTUNE TM D5535 and INTUNE TM D10510. In a preferred embodiment, the propylene-based block copolymer blend is INTUNE TM D5545. In an embodiment, the propylene-based block copolymer blend is INTUNE TM D5535.
[0227] 3. Polyisobutylene block elastomer
[0228] In some embodiments, the soft thermoplastic elastomer is a block copolymer of polyisobutylene. They are composed of rigid thermoplastic sequences connected by flexible elastomeric sequences of polyisobutylene. They are typically triblock elastomers in which two rigid segments are connected by flexible segments of isobutylene. The rigid segments and the flexible segments can be arranged linearly, in a star-shaped manner, or in a differentiated manner. Preferably, the polyisobutylene block of the polyisobutylene block elastomer or block copolymer additionally has a glass transition temperature ("Tg") less than or equal to -20°C, more preferably less than -40°C. The Tg of the polyisobutylene block of the block copolymer is also more preferably lower than -50°C.
[0229] The thermoplastic block or blocks of the polyisobutylene block elastomer (hereinafter referred to as "hard segments") are thus composed of at least one polymerized monomer based on unsubstituted or substituted styrene; among the substituted styrenes, mention may be made, for example, of methylstyrene (for example o-, m- or p-methylstyrene, α-methylstyrene, α,2-dimethylstyrene, α,4-dimethylstyrene or diphenylethylene), p-(tert-butyl)styrene, chlorostyrene (for example o-, m-, p-chlorostyrene, 2,4-dichlorostyrene, 2,6-dichlorostyrene or 2,4,6-trichlorostyrene), bromostyrene (for example o-, m-, p-bromostyrene, 2,4-dibromostyrene, 2,6-dibromostyrene or 2,4,6-tribromostyrene), fluorostyrene (for example o-, m-, p-fluorostyrene), 2,4-difluorostyrene, 2,6-difluorostyrene or 2,4,6-trifluorostyrene) or p-hydroxystyrene.
[0230] In some preferred embodiments, the polyisobutylene block elastomer is a block copolymer of polystyrene and polyisobutylene. Preferably, this block copolymer is a styrene / isobutylene diblock copolymer. In a more preferred embodiment, this block copolymer is a styrene / isobutylene / styrene triblock copolymer (abbreviated as "SIBS"). Below the specified minimum thermoplastic content, the thermoplastic properties of the elastomer are likely to be greatly reduced, while above the recommended maximum content, the elasticity will be affected. For these reasons, the styrene content is more preferably between 10% and 40%, in particular between 15% and 35%. Preferably, the glass transition temperature of the hard segment formed by the styrene polymerized monomer is greater than or equal to 100°C.
[0231] In some embodiments, the Shore A hardness of the SIBS elastomer is 10 to 90, or 15 to 70, or 15 to 60, or 20 to 60, or 25 to 50. The tensile strength at break of the SIBS elastomer is 4 MPa to 15 MPa, or 4 MPa to 20 MPa, or 5 MPa to 20 MPa, or 6 MPa to 19 MPa, or 10 MPa to 20 MPa. In some embodiments, the melt flow rate (230°C, 2.16 kg) of the SIBS elastomer is 0.05 to 30, or 0.07 to 25, or 0.09 to 20, or 0.1 to 10, or 0.1 to 5, or 0.1 to 2. In some embodiments, the compression deformation of the SIBS elastomer at 70°C is 20 to 100, or 30 to 95, or 40 to 80, or 50 to 70. In some preferred embodiments, the elastomer is commercially available under the name "Sibstar" by Kaneka, such as SIB and SIBS (e.g., SIBS is "Sibstar 103T", "Sibstar 102T", "Sibstar 073T" or "Sibstar 072T", or SIB is "Sibstar 042D"). They and their synthesis have been described in, for example, patent literature (EP 731 112, U.S. Patent No. 4,946,899 and U.S. Patent No. 5,260,383). They were first developed for biomedical applications, and various specific applications for TPSI elastomers were then described, such as medical equipment, motor vehicle or household appliance parts, wire sheaths, airtight parts or elastic parts (see, for example, EP 1 431 343, EP 1 561 783, EP 1 566 405 and WO 2005 / 103146).
[0232] 4. Propylene-based elastomers
[0233] Propylene-based polymers, such as propylene-based elastomers ("PBEs"). The PBEs comprise propylene and from about 5 wt% to about 30 wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins. For example, the comonomer units may be derived from ethylene, butene, pentene, hexene, 4-methyl-1-pentene, octene, or decene. In a preferred embodiment, the comonomer is ethylene. In some embodiments, the PBE consists essentially of propylene and ethylene, or consists only of propylene and ethylene. Some of the embodiments described below are discussed with reference to ethylene as the comonomer, but these embodiments are equally applicable to PBEs containing other alpha-olefin comonomers. In this regard, the copolymers may be simply referred to as PBEs with reference to ethylene as the alpha-olefin.
[0234] The PBE may contain at least about 5 wt%, at least about 6 wt%, at least about 7 wt%, at least about 8 wt%, at least about 9 wt%, or at least about 10 wt% of alpha-olefin derived units based on the total weight of the PBE. The PBE may contain up to about 30 wt%, or up to about 25 wt%, up to about 22 wt%, up to about 20 wt%, up to about 17 wt%, up to about 15 wt%, up to about 13 wt%, or up to about 12 wt% of alpha-olefin derived units based on the total weight of the PBE. In some embodiments, the PBE may contain about 5 wt% to about 25 wt%, about 6 wt% to about 22 wt%, about 7 wt% to about 20 wt%, about 8 wt% to about 17 wt%, about 9 wt% to about 15 wt%, about 9 wt% to about 13 wt%, or about 10 wt% to about 12 wt% of alpha-olefin derived units based on the total weight of the PBE.
[0235] The PBE may contain at least about 70 wt%, or at least about 75 wt%, at least about 78 wt%, at least about 80 wt%, at least about 83 wt%, at least about 85 wt%, at least 87 wt%, or at least 88 wt% of propylene derived units based on the total weight of the PBE. The PBE may contain up to about 95 wt%, up to about 94 wt%, up to about 93 wt%, up to about 92 wt%, up to about 91 wt%, or up to about 90 wt% of propylene derived units based on the total weight of the PBE.
[0236] The Tm of the PBE (determined by DSC) may be less than about 110°C, less than about 100°C, less than about 90°C, less than about 80°C, less than about 70°C, less than about 65°C, less than about 60°C. The Tm of the PBE may be about 20°C to about 90°C, about 30°C to about 80°C, about 40°C to about 70°C, or about 50°C to about 65°C, where desirable ranges may include ranges from any lower limit to any upper limit. In some embodiments, the Tm of the PBE may be about 55°C to about 70°C, or about 57°C to about 68°C, or about 60°C to about 65°C, where desirable ranges may include ranges from any upper limit to any lower limit. In some embodiments, the Tm of the PBE may be about 45°C to about 65°C, or about 50°C to about 60°C, or about 52°C to about 58°C, where desirable ranges may include ranges from any upper limit to any lower limit.
[0237] The PBE may be characterized by its heat of fusion (HD, as determined by DSC). The PBE may have an Hf of at least about 1.0 J / g, at least about 3.0 J / g, at least about 5.0 J / g, at least about 7.0 J / g, at least about 10.0 J / g, at least about 12 J / g, at least about 15 J / g, at least about 20 J / g, or at least about 25 J / g. The PBE may be characterized by an Hf of less than about 60 J / g, less than about 50 J / g, less than about 40 J / g, less than about 35 J / g, less than about 30 J / g, less than about 25 J / g, less than about 20 J / g, less than about 15 J / g. The Hf of the PBE may be from about 1.0 J / g to about 50 J / g, or from about 3.0 J / g to about 40 J / g, or from about 5.0 J / g to about 35 J / g, or from about 10.0 J / g to about 30 J / g, where desirable ranges may include ranges from any lower limit to any upper limit. In some embodiments, the Hf of the PBE may be from about 1.0 J / g to about 25 J / g, from about 5.0 J / g to about 20 J / g, from about 10 J / g to 20 J / g, or from about 12 J / g to about 18 J / g, where desirable ranges may include ranges from any lower limit to any upper limit. In some embodiments, the PBE may have a Hf of 5.0 J / g to about 40 J / g, about 10.0 J / g to about 35 J / g, about 15 J / g to about 35 J / g, or about 20 J / g to about 30 J / g, or about 25 J / g to about 30 J / g, where desirable ranges may include ranges from any lower limit to any upper limit.
[0238] The density of the PBE at room temperature can be from about 0.84 g / cm3 to about 0.92 g / cm3, from about 0.85 g / cm3 to about 0.90 g / cm3, or from about 0.86 g / cm3 to about 0.88 g / cm3, as measured according to ASTM D-1505 test method, where desired ranges may include ranges from any lower limit to any upper limit.
[0239] The PBE may have a melt index (MI) (ASTM D-1238, 2.16 kg @ 190°C) of about 25 g / 10 min or less, about 10 g / 10 min or less, about 8.0 g / 10 min or less, about 5.0 g / 10 min or less, or about 2.0 g / 10 min or less. In some embodiments, the PBE has a MI of about 0.5 g / 10 min to about 3.0 g / 10 min or about 0.75 g / 10 min to about 2.0 g / 10 min, where desired ranges may include ranges from any lower limit to any upper limit. In some embodiments, the MI of the PBE is from about 1.0 g / 10 min to about 25 g / 10 min, or from about 1.0 g / 10 min to about 10 g / 10 min, or from about 2.0 g / 10 min to about 6.0 g / 10 min, or from about 2.5 g / 10 min to about 5.0 g / 10 min, or from about 2.5 g / 10 min to about 25 g / 10 min, or from about 2.5 g / 10 min to about 10 g / 10 min, where desirable ranges may include ranges from any lower limit to any upper limit.
[0240] The melt flow rate (MFR) of the PBE can be greater than about 0.5 g / 10 min, greater than about 1.0 g / 10 min, greater than about 1.5 g / 10 min, greater than about 2.0 g / 10 min, or greater than about 2.5 g / 10 min, measured according to ASTM D-1238 (2.16 kg weight @ 230°C). The MFR of the PBE can be less than about 25 g / 10 min, less than about 15 g / 10 min, less than about 10 g / 10 min, less than about 7 g / 10 min, or less than about 5 g / 10 min. The MFR of the PBE can be from about 0.5 g / 10 min to about 15 g / 10 min, from about 1.0 g / 10 min to about 10 g / 10 min, or from about 1.5 g / 10 min to about 9 g / 10 min, where desired ranges may include ranges from any lower limit to any upper limit. In some embodiments, the MFR of the PBE may be from about 2.5 g / 10 min to about 25 g / 10 min, or from about 2.5 g / 10 min to about 15 g / 10 min, or from about 2.5 g / 10 min to about 12 g / 10 min, or from about 5.0 g / 10 min to about 10 g / 10 min, where desirable ranges may include ranges from any lower limit to any upper limit. In some embodiments, the MFR of the PBE may be from about 0.5 g / 10 min to about 7.0 g / 10 min, or from about 1.0 g / 10 min to about 6.0 g / 10 min, or from about 2.0 g / 10 min to about 5.0 g / 10 min, where desirable ranges may include ranges from any lower limit to any upper limit.
[0241] The Shore D hardness of the PBE may be less than about 50, or less than about 45, or less than about 40, or less than about 35. The Shore D hardness of the PBE may be from about 10 to about 50, or from about 15 to about 45, or from about 20 to about 40, or from about 25 to about 35, where desired ranges may include ranges from any lower limit to any upper limit. The Shore A hardness of the PBE may be greater than 10, or greater than 20, or greater than 40, or greater than 50; for example, between 40 and 90.
[0242] The Vicat softening temperature of the PBE may be less than 100° C., or less than 90° C., or less than 80° C., or less than 75° C., or less than 70° C. The Vicat softening temperature of the PBE may be at least 30° C., or at least 40° C., or at least 50° C., or at least 60° C.
[0243] The PBE is preferably produced using homogeneous conditions, such as a continuous solution polymerization process. Exemplary methods for producing propylene-based polymers can be found in U.S. Pat. Nos. 6,881,800, 7,803,876, 8,013,069, and 8,026,323, and PCT Publications WO 2011 / 087729, WO 2011 / 087730, and WO 2011 / 087731. In some embodiments, the thermoplastic component of the TPV composition may include propylene and ethylene or a higher α-olefin as described above, or with C 10 To C 20 Impact copolymers and / or random copolymers of dienes. These propylene copolymers may have a comonomer content of from about 1% to about 30% by weight of the polymer, including any values and subsets therebetween, as described, for example, in U.S. Pat. No. 6,867,260, which is incorporated herein by reference in its entirety. Suitable commercially available thermoplastic components include those sold under the trade name VISTAMAXX TM Olefin elastomers (available from ExxonMobil Chemical Company, Houston, Texas, or VERSIFY TM Available from The Dow Chemical Company, Midland, Michigan).
[0244] 5.4-Methyl-1-pentene / α-olefin copolymer
[0245] The 4-methyl-1-pentene / α-olefin copolymer according to the present invention comprises:
[0246] 5 mol% to 95 mol% of (i) structural units derived from 4-methyl-1-pentene,
[0247] 95 mol% to 5 mol% of (ii) structural units derived from at least one type of α-olefin selected from olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene, and
[0248] 0 mol% to 10 mol% of (iii) is derived from a structural unit of a non-conjugated polyene, provided that the sum of the structural units (i), (ii) and (iii) is 100 mol%.
[0249] The copolymer comprises: a structural unit of 4-methyl-1-pentene, the content of which is preferably 10 mol% to 90 mol%, more preferably 15 mol% to 85 mol%, still more preferably 15 mol% to 80 mol%, and most preferably 15 mol% to 75 mol%; and a structural unit (ii), the amount of which is preferably 90 mol% to 10 mol%, more preferably 85 mol% to 15 mol%, still more preferably 85 mol% to 20 mol%, and most preferably 85 mol% to 25 mol%, provided that the sum of the structural units (i) and (ii) is 100 mol%. In the present invention, unless otherwise specified, "α-olefin having 2 to 20 carbon atoms" does not include 4-methyl-1-pentene. At the same time, any other copolymerization components may be contained therein without prejudice to the purpose of the present invention; and its embodiments are all within the scope of the present invention.
[0250] In addition, the copolymer meets at least the following requirements:
[0251] The tensile modulus (YM) of the copolymer is 0.1 MPa to 1000 MPa, preferably 0.1 MPa to 500 MPa, more preferably 0.1 MPa to 300 MPa, and still more preferably 0.1 MPa to 200 MPa. When the tensile modulus is within the above range, for example, mechanical properties, toughness, flexibility, and stress absorption are excellent.
[0252] As measured by DSC, the melting point (Tm) of the copolymer is preferably lower than 110°C or not observed, more preferably lower than 100°C or not observed, and still more preferably lower than 85°C or not observed. The melting point of copolymer (A) can be arbitrarily changed according to the type and composition of the comonomer. When the melting point is within the above range, flexibility and toughness are excellent.
[0253] The density of the copolymer, as measured according to ASTM D 1505 (water displacement method), is preferably in the range of 0.810 to 0.850 g / cm3, more preferably 0.820 to 0.850 g / cm3, more preferably 0.830 to 0.850 g / cm3.
[0254] Preferably, the copolymer meets the following requirements (c1) and (e):
[0255] (c1): The tensile modulus (YM) is 0.1 MPa to 300 MPa, preferably 0.1 MPa to 250 MPa, and more preferably 0.3 MPa to 200 MPa. When the tensile modulus is within the above range, mechanical properties, toughness, flexibility, and stress absorption are excellent.
[0256] (e): Change ΔHS in Shore A hardness between immediately after measurement and 15 seconds after measurement is 10 to 50, preferably 15 to 50, more preferably 20 to 50. The change in Shore A hardness is obtained according to JIS K 6253 as follows.
[0257] ΔHS = (Shore A hardness 15 seconds after measurement - Shore A hardness immediately after measurement)
[0258] The ΔHS value may be arbitrarily changed according to the type and composition of the comonomer. When ΔHS is within the above range, stress absorption and stress relaxation are excellent.
[0259] The 4-methyl-1-pentene / α-olefin copolymer (A2) comprises:
[0260] 33 mol % to 80 mol %, preferably 50 mol % to 75 mol % of structural unit (i),
[0261] 67 mol % to 20 mol %, preferably 50 mol % to 25 mol % of structural unit (ii), and
[0262] 0 mol % to 10 mol %, preferably 0 mol % to 5 mol %, of structural unit (iii), provided that the sum of structural units (i), (ii) and (iii) is 100 mol %; and
[0263] In addition to satisfying at least the requirements (a) to (d), any one or more of the Shore A hardness and the Shore D hardness of the following requirement (e1) are also satisfied.
[0264] Since the 4-methyl-1-pentene / α-olefin copolymer (A2) has excellent stress relaxation, the 4-methyl-1-pentene / α-olefin copolymer is preferred.
[0265] (e1): The ΔHS difference between the Shore A hardness just after the indenter contacts and the Shore A hardness 15 seconds after the indenter contacts is 15 to 50, preferably 20 to 50, and more preferably 23 to 50; or, the ΔHS difference between the Shore D hardness just after the indenter contacts and the Shore D hardness 15 seconds after the indenter contacts is 5 to 50, preferably 8 to 50, and more preferably 10 to 50.
[0266] Straight chain α-olefins are those having 2 to 20 carbon atoms, preferably 2 to 15 carbon atoms, more preferably 2 to 10 carbon atoms, examples of which include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene and 1-eicosene; and ethylene, propylene, 1-butene, 1-pentene, 1-hexene and 1-octene are preferred. In the present invention, straight chain α-olefins having 2 to 10 carbon atoms are preferred in terms of flexibility, stress absorption, stress relaxation, etc.; and ethylene, propylene, 1-butene, 1-pentene, 1-hexene and 1-octene are more preferred. In terms of providing high stress absorption and polyolefin modification properties, ethylene and propylene are even more preferred; and propylene is particularly preferred. Suitable commercially available 4-methyl-1-pentene / propylene copolymer components include those sold under the trade name Absortomer TM Those of (available from Mitsui Chemical).
[0267] In some embodiments, the 4-methyl-1-pentene / propylene copolymer is Absortomer EP-1001; in some embodiments, the 4-methyl-1-pentene / propylene copolymer is Absortomer EP-1013.
[0268] Processing oils and other additives
[0269] Hydrocarbon resin
[0270] The thermoplastic vulcanizate compositions of the present invention may also contain a "hydrocarbon resin" (HCR) having a high glass transition temperature (Tg) or a high softening point, or both. It is contemplated that the hydrocarbon resin may be any of a number of different types of polymers as described below, provided that it possesses the necessary properties.
[0271] The hydrocarbon resin may be a heat polymerized dicyclopentadiene resin, preferably hydrogenated to achieve clarity and minimize discoloration. The hydrocarbon resin may also be a catalytically polymerized resin made using a Friedel-Crafts catalyst such as a boron halide or an aluminum halide. The hydrocarbon resin may be an alicyclic resin or the hydrocarbon resin may contain an appropriate level of aromatic compounds.
[0272] A particularly preferred hydrocarbon resin is OPPERAPR104 provided by ExxonMobil Chemical Company, which has a Tg of 65°C and a softening point in the range of 119°C to 125°C. Preferably, the hydrocarbon resin is miscible with two or at least one of the polymer components (FPC and SPC), as described below. In addition, the hydrocarbon resin itself should be clear, preferably colorless or transparent; preferably, it is a water-white alicyclic hydrocarbon resin.
[0273] In at least some embodiments, the hydrocarbon resin has a high glass transition temperature, Tg, which is at least 1°C higher than the Tg of the composition (including processing oil, if present) in the absence of the hydrocarbon resin. Alternatively, in some embodiments, the Tg of the hydrocarbon resin is higher than the Tg of each of the other individual polymers.
[0274] In certain embodiments, the glass transition temperature Tg of the hydrocarbon resin is a Tg in a range having a low value of 20° C., or 30° C., or 40° C. and a high value of 70° C., or 80° C., or 90° C. The hydrocarbon resin preferably has a glass transition temperature greater than 20° C. as measured by DSC.
[0275] In certain embodiments, the softening point of the hydrocarbon resin is within a range of a lower limit of 80, 120, or 125° C. and an upper limit of 140, 150, or 180° C. The softening point (° C.) is measured as Ring and Ball softening point according to ASTM E-28.
[0276] Preferably, hydrocarbon resin is amorphous and glassy, has low molecular weight.Preferably, the molecular weight of hydrocarbon resin is lower than the molecular weight of any one of co-polymers.In certain embodiments, the number average molecular weight (Mn) of hydrocarbon resin can be in the range of 5000, or 2000, or 1000 with an upper limit and 200, or 400, or 500 with a lower limit, a weight average molecular weight (Mw) can be in the range of 500 to 5000, a Z average molecular weight (Mz) can be in the range of 500 to 10,000, and a polydispersity (PD) measured by Mw / Mn is 1.5 to 3.5, wherein Mn, Mw and Mz are measured by size exclusion chromatography (SEC).
[0277] The hydrocarbon resin should be present in the composition in an amount ranging from a lower limit of 1 wt%, 5 wt% or 10 wt% based on the total weight of the composition to an upper limit of 30 wt% or 25 wt% or 20 wt% or 18 wt% or 15 wt% based on the total weight of the composition.
[0278] Hydrocarbon resins can include any of the following compounds, as long as they are otherwise suitable, such as having the necessary properties described elsewhere herein. In addition, they should provide (or at least not reduce) transparency. Examples of hydrocarbon resins include aliphatic hydrocarbon resins, hydrogenated aliphatic hydrocarbon resins, aromatic modified aliphatic hydrocarbon resins, hydrogenated aromatic modified aliphatic hydrocarbon resins, polycyclopentadiene resins, hydrogenated polycyclopentadiene resins, alicyclic hydrocarbon resins, hydrogenated alicyclic resins, alicyclic / aromatic hydrocarbon resins, hydrogenated alicyclic / aromatic hydrocarbon resins, hydrogenated aromatic hydrocarbon resins, maleic acid / maleic anhydride modified tackifiers, polyterpene resins, hydrogenated polyterpene resins, aromatic modified polyterpene resins, Hydrogenated aromatic modified polyterpene resins, terpene-phenol resins, hydrogenated terpene-phenol resins, rosin resins, hydrogenated rosin resins, rosin ester resins, hydrogenated rosin ester resins, wood rosin resins, hydrogenated wood rosin resins, wood rosin ester resins, hydrogenated wood rosin ester resins, tall oil rosin resins, hydrogenated tall oil rosin resins, tall oil rosin ester resins, hydrogenated tall oil rosin ester resins, rosin acid resins, hydrogenated rosin acid resins, and mixtures of two or more thereof. These materials are preferably low molecular weight materials having a molecular weight (Mw) of less than 10,000, more preferably less than 5,000, more preferably less than 2500, more preferably less than 2000, suitably in the range of 1 and 1000, more preferably between 500 and 2000, more preferably between 500 and 1000.
[0279] Specific examples of commercially available hydrocarbon resins include: Oppera PR 100, 101, 102, 103, 104, 105, 106, 111, 112, 115 and 120 materials, and Oppera PR 131 hydrocarbon resin, all available from ExxonMobil Chemical Company; ARKON TM M90, M100, M115, M135 and SUPER ESTER TM Rosin esters, available from Arakawa Chemical Co., Ltd., Japan; SYLVARES TM Phenol-modified styrene resins and phenol-modified methylstyrene resins, styrenated terpene resins, ZONATAC terpene-aromatic resins, and terpene-phenol resins are available from Arizona Chemical Company; SYLVATAC TM and SYLVALITE TM Rosin esters, available from Arizona Chemical Company; NORSOLENE TM Aliphatic aromatic resin, available from Cray Valley, France; DERTOPHENE TM Terpene phenol resins, available from Landes DRT Chemical Company, France; EASTOTAC TM Resin, PICCOTACT TMC5 / C9 resin, REGALITE TM REGALREZ TM Aromatic resins and REGALITE TM Cycloaliphatic / aromatic resins, available from Eastman Chemical Company, Kingsport, Tennessee; WINGTACK TM ET and EXTRA, available from Goodyear Chemical Company; FORAL TM 、PENTALYN TM and PERMALYN TM Rosin and rosin esters, available from Hercules (now Eastman Chemical Company); QUINTONE TM Acid-modified C5 resin, C5 / C9 resin, and acid-modified C5 / C9 resin, available from Nippon Zeon, Japan; and LX TM Mixed aromatic / cycloaliphatic resins available from Neville Chemical Company; CLEARON hydrogenated terpene aromatic resins available from Yasuhara. The foregoing examples are merely illustrative and are not intended to be limiting in any way.
[0280] These commercial compounds typically have a ring and ball softening point of about 10°C to 200°C, more preferably about 10°C to 160°C, more preferably about 25°C to 140°C, more preferably about 60°C to 130°C, more preferably about 60°C to 130°C, more preferably about 90°C to 130°C, more preferably about 80°C to 120°C, more preferably about 85°C to 115°C, and more preferably about 90°C to 110°C, as measured according to ASTM E-28, wherein any upper limit and any lower limit of the softening point can be combined to obtain a preferred softening point range. For hydrocarbon resins, a convenient measurement standard is the ring and ball softening point determined according to ASTM E-28.
[0281] Processing oil
[0282] In some embodiments, the process oil comprises low molecular weight C4 olefins (including normal butene, 2-butene, isobutylene and butadiene and mixtures thereof). When the oligomer comprises isobutylene and / or 1-butene and / or 2-butene, this material is referred to as a "polybutene" liquid. It is commonly used as an additive for polyolefins; for example, for introducing viscosity or as a processing aid. The ratio of C4 olefin isomers may vary depending on the manufacturer and grade, and the material may or may not be hydrogenated after synthesis. In some cases, the polybutene liquid is a polymer of a C4 residual liquid stream. In other cases, the polybutene liquid is essentially composed of polyisobutylene or poly (normal butene) oligomers. Typically, the number average molecular weight of the polybutene liquid is less than 15,000 g / mol, typically less than 5,000 g / mol or even less than 1,000 g / mol. They are described, for example, in SYNTHETIC LUBRICANTS AND HIGH-PERFORMANCE FUNCTIONAL FLUIDS 357-392 (Leslie R. Rudnick & Ronald L. Shubkin, ed., Marcel Dekker 1999). Commercial sources of polybutene include Ineos (Indopol grades) and Infineum (C series grades). When the C4 olefin is only isobutylene, the material is referred to as "polyisobutylene" or PIB. Commercial sources of PIB include Texas Petrochemical (TPC enhanced PIB grades). When the C4 olefin is only 1-butene, the material is referred to as "poly-n-butene" or PNB. The properties of some liquids prepared from C4 olefins are summarized in the table below. It is worth noting that grades with a flash point of 200°C or more also have a pour point greater than -10°C and / or a VI less than 120.
[0283] Commercial Examples of C4 Olefin Oligomers KV@Pour Flash 100℃.,Point,Specific Point,Grade cSt VI℃.gravity℃.TPC 137(PIB)6 132-51 0.843 120 TPC 1105(PIB)220 145-6 0.893 200 TPC 1160(PIB)660 190 3 0.903 230 Ineos Indopol H-25 52 87-230.869~150 Ineos Indopol H-50 108 90-13 0.884~190 Ineos Indopol H-100 218121-7 0.893~210 Infineum C9945 11 74*-34 0.854 170 Infineum C9907 78 103*-150.878 204 Infineum C9995 230 131*-7 0.888 212 Infineum C9913 630 174*10 0.888240 *Estimated based on kinematic viscosity at 100°C and 38°C.
[0284] Curing agent
[0285] The composition comprises a curing agent, which includes an amine curing agent, wherein one or more amine curing agents are selected from (6-aminohexyl) carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine) carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N-diethyl-p-phenylenediamine. Most preferably, the material is selected from 4,4'-methylene-bis-(cyclohexylamine) carbamate (trade name Commercially available from RTVANDERBILT CO., Norwalk, Connecticut).
[0286] Medicinal plug composition
[0287] The pharmaceutical plug may include the thermoplastic elastomer composition described herein, the thermoplastic elastomer composition comprising an at least partially crosslinked thermoplastic elastomer composition, the thermoplastic elastomer composition comprising: one or more BIMSMs having a Mooney viscosity (ML 1+8, 125° C.) of 30 MU to 50 MU according to the ASTM D1646 test method, and / or a benzyl bromide content of 0.3 mol% to 5 mol%; 10 phr to 50 phr of PPH, the PPH having a a melt flow rate (MFR) (230°C / 2.16kg) of 0.2 to 2000 g / 10min (or 0.5 to 1500 g / 10min, or 0.5 to 1000 g / 10min, or 0.5 to 500 g / 10min, or 0.5 to 100 g / 10min, more preferably 0.5 to 20 g / 10min) according to the D1238 test method; one or more curing agents (e.g., present at 0.1 to 15 phr or 0.5 to 10 phr); 10 to 100 phr (before and / or after curing) of a processing oil comprising a polyisobutylene polymer; and optional additional additives; and wherein the thermoplastic elastomer composition is cured using a phenolic resin-based curing system, a sulfur-based curing system, or an amine-based curing system.
[0288] The pharmaceutical plug may comprise a thermoplastic elastomer composition as described herein, comprising an at least partially crosslinked elastomeric phase, the thermoplastic elastomer composition comprising: one or more BIMSMs having a Mooney viscosity (ML 1+8, 125°C) of 30MU to 50MU according to the ASTM D1646 test method, and / or a benzyl bromide content of 0.3 mol% to 5 mol%; 10 phr to 90 phr of a thermoplastic phase; one or more curing agents (e.g., present at 0.1 phr to 15 phr or 0.5 phr to 10 phr); 10 phr to 100 phr (before and / or after curing) of a processing oil comprising a polyisobutylene polymer; and optional additional additives; and wherein the thermoplastic elastomer composition is cured using a phenolic resin-based curing system, a sulfur-based curing system, or an amine-based curing system.
[0289] To form a thermoplastic elastomer composition according to at least one embodiment of the present disclosure, the thermoplastic elastomer composition can be compounded or otherwise mixed according to a suitable mixing method; and molded into a pharmaceutical article, wherein crosslinking and / or curing occurs according to known methods and at known points during the method of forming a pharmaceutical plug and / or related thermoplastic elastomer composition.
[0290] Exemplary Embodiments
[0291] Embodiments disclosed herein include:
[0292] A: A thermoplastic elastomer composition comprising: one or more brominated isobutylene p-methyl-styrene terpolymers; and 20 to 50 parts by weight or 10 to 80 parts by weight of a thermoplastic phase per hundred parts by weight of rubber (phr); wherein the thermoplastic elastomer composition is cured using a phenolic resin-based curing system, a sulfur-based curing system, or an amine-based curing system.
[0293] B: A thermoplastic vulcanizate composition comprising: an elastomeric phase comprising one or more brominated isobutylene para-methyl-styrene terpolymers; 10 to 90 parts by weight per hundred parts by weight of rubber (phr) of a thermoplastic phase comprising a blend of one or more thermoplastic polyolefins and one or more soft thermoplastic elastomers, wherein the soft thermoplastic elastomer has a Shore A hardness of 20 to 96, a Shore D hardness of 20 to 50, and a tensile strength at break of 2 MPa to 20 MPa; and 10 to 100 phr of a processing oil; wherein the elastomeric phase is cured using a phenolic resin-based cure system or an amine-based cure system.
[0294] C: A pharmaceutical stopper, comprising: a thermoplastic vulcanizate rubber composition, comprising: an elastomeric phase comprising one or more brominated isobutylene paramethyl-styrene terpolymers; 10 to 90 parts by weight of a thermoplastic phase per hundred parts by weight of rubber (phr), the thermoplastic phase comprising a blend of one or more thermoplastic polyolefins and one or more soft thermoplastic elastomers, wherein the soft thermoplastic elastomer has a Shore A hardness of 20 to 96, a Shore D hardness of 20 to 50, and a tensile strength at break of 2 MPa to 20 MPa; and 10 to 100 phr of a processing oil; wherein the elastomeric phase is cured using a phenolic resin-based curing system or an amine-based curing system.
[0295] Each of embodiments A, B and C may have one or more of the following additional elements in any combination:
[0296] Element 1: wherein the thermoplastic phase is present in an amount of 30 to 80 phr.
[0297] Element 2: wherein the process oil is present at 40 phr to 80 phr or 50 phr to 70 phr.
[0298] Element 3: wherein the phenolic resin-based curing system comprises a curing agent, which curing agent includes one or more of the following: 0.1 phr to 20 phr of stannous chloride; 0.1 phr to 15 phr of metal oxide; 0.05 phr to 10 phr of stearic acid; and 0.5 phr to 20 phr of phenolic resin.
[0299] Element 4: The phenolic resin is an alkylphenolic resin.
[0300] Element 5: The sulfur curing system comprises a sulfur curing agent, which comprises one or more of the following: 0.1 phr to 10 phr of MBTS; 0.01 phr to 5 phr of sulfur; 0.1 phr to 10 phr of metal oxide; and 0.5 phr to 15 phr of stearic acid.
[0301] Element 6: The metal oxide is selected from magnesium oxide (MgO), zinc oxide (ZnO), manganese oxide (MnO), sodium oxide (Na2O), iron oxide (Fe2O3), silicon dioxide (SiO2), calcium oxide (CaO), aluminum oxide (Al2O3) or a mixture thereof.
[0302] Element 7: wherein the amine cure system comprises one or more amine curing agents present in an amount of 0.1 phr to 10 phr.
[0303] Element 8: One or more amine curing agents are selected from (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
[0304] Element 9: wherein the clay is present in an amount of 1 to 30 phr.
[0305] Element 10: wherein the specific gravity of the composition at about 23°C is 0.8 g / cm 3 Up to 1g / cm 3 .
[0306] Element 11: wherein the composition has 0.01% to 0.03% water vapor (%).
[0307] Element 12: The composition has an extrusion surface Ra (μm) of 140 to 190.
[0308] Element 13: The composition has a tensile strength (MPa) of 1 to 10.
[0309] Element 14: wherein the composition has a 100% modulus (MPa) of 1 to 5.
[0310] Element 15: The composition has an elongation at break (%) of 100 to 500.
[0311] Element 16: wherein the composition has a permeability (cc.mm / m 2 .day.mmHg).
[0312] Element 17: The composition has a punching force (maximum force (N) among 10 punctures) of 1 to 10.
[0313] As non-limiting examples, exemplary combinations suitable for A, B, C include: A, B or C with 1 and 2; A, B or C with 1, 2 and 7; A, B or C with 8 and 9; A, B or C with 10, 11 and 17, etc.
[0314] Embodiments of the present disclosure also include thermoplastic vulcanizates that exhibit improved coring performance, self-sealing, low impact forces, excellent oxygen barrier properties, and improved compression set at elevated temperatures.
[0315] It should be understood that although the invention has been described in conjunction with its specific embodiments, the foregoing description is intended to illustrate rather than limit the scope of the invention. Other aspects, advantages and improvements will be apparent to those skilled in the art to which the invention pertains.
[0316] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should not be interpreted in any way as limiting or defining the scope of the present invention.
[0317] Example
[0318] Tension set is measured according to ASTM D-412. Permeability is in cc·mm / m 2 · Day·mmHg, and measured as follows: Using WINPERM with MOCON permeability system software designed to measure the rate of oxygen penetration through the test material TMThe barrier and permeability properties of elastomeric compounds were tested using the MOCON OX-TRAN 2 / 61. The elastomeric compounds were molded into 0.3 mm round film specimens with a diameter of approximately 1 7 / 8 inches and tested using air. The transmission rate was used to calculate the permeability coefficient. The specific gravity was measured at 23°C according to the ASTM D-792 method. Tensile and elongation were measured according to the ISO 37 method. According to the ExxonMobil internal test method, a stylus profilometer was used to measure the extruded surface Ra (surface roughness). Water vapor (%) was measured according to the ASTM D-7191-05 method. Hardness was measured according to the ASTM D-2240 method. Tensile modulus was measured according to the ISO 37 method. Punch force, self-sealing and fragmentation properties were measured according to the method specified in the United States Pharmacopeia (USP) 381 "Elastomer Closures for Injection" standard. Surface roughness was tested on a Model Perthometer S2 surface measuring device.
[0319] Table 1 shows the thermoplastic elastomer compositions E1-E3 of the present invention, as well as different curing systems of the thermoplastic elastomer compositions, a phenolic resin curing system (E1), a sulfur curing system (E2) and an amine curing system (E3). Stannous chloride is a curing accelerator. Stearic acid is a vulcanization activator. MBTS is 2-2'-disulfide bis(benzothiazole), which is a sulfur vulcanization accelerator. ICECAP TM Clays are mineral rubber fillers used to deliver specific ingredients, such as stannous chloride powder, to the correct location during reactive extrusion.
[0320] BIMSM-1: brominated copolymer of isobutylene and p-methylstyrene. Mooney viscosity (ML 1+8, 125°C) = 45; benzyl bromide = 1.20 (mol%); calcium (wt%) = 0.09. Available from ExxonMobil under the trade name Exxpro.
[0321] BIMSM-2: brominated copolymer of isobutylene and p-methylstyrene. Mooney viscosity (ML 1+8, 125°C) = 35; benzyl bromide = 0.75 (mol%); calcium (wt%) = 0.09. Available from ExxonMobil under the trade name Exxpro.
[0322] PP-1: a homopolymer PP having a low melt flow rate (230°C / 2.16 kg) of 0.83 g / 10 min, which provides high melt strength and resistance to softening at high temperatures, available from ExxonMobil.
[0323] PP-2: Homopolymer PP with a melt flow rate (230° C., 2.16 kg) of 17 g / 10 min (according to ASTM D-1238), available from Braskem.
[0324] Amine Cure-1: A chemical containing 4,4,-bis(aminocyclohexyl)methane carbamate, available from Vanderbilt Chemicals.
[0325] INDOPOL TM H100 is a polyisobutylene (PIB) polymer used as a processing aid due to its miscibility in BIMSM polymers and its acceptance in pharmaceutical applications where other oils and plasticizers are generally not allowed. The terpolymer content in all formulations (Examples E1-E3) was 100 phr, and INDOPOL TM The total content of H100 is 64.3 phr. The polypropylene homopolymer matrix of the thermoplastic elastomer composition allows melt flow and injection molding. The brominated isobutylene p-methyl-styrene terpolymer portion (i.e., BIMSM portion) of the thermoplastic elastomer composition provides the physical properties required for pharmaceutical stopper applications (e.g., low permeability, resealability, low fragmentation, etc.).
[0326] The above description lists different scenarios to adjust the formulation to suit the requirements. These adjustments are interchangeable between the different curing systems. Compositions E2 and E3 were produced in a Brabender mixer, while composition E1 was produced in a twin screw extruder.
[0327] Table 1. Blend composition and conditions
[0328] Initial preparation E1 E2 E3 BIMSM-1(phr) 100.0 100.0 BIMSM-2(phr) 100.0 <![CDATA[ICECAP TM Clay (phr)]]> 5.0 5.0 5.0 Stannous chloride powder (phr) 1.3 <![CDATA[ICECAP TM Clay (phr)]]> 5.0 5.0 5.0 Magnesium oxide powder (phr) 2.0 0.5 Zinc oxide (phr) 2.0 2.0 Stearic acid (phr) 1.0 1.0 <![CDATA[Phenolic resin SP-1045 TM (phr)]]> 3.5 MBTS(phr) 1.5 Sulfur (phr) 0.5 Amine curing - 1(phr) 0.8 PP-1(phr) 30.0 PP-2(phr) 37.0 37.0 <![CDATA[INDOPOL TM H100 (before curing) (phr)]]> 42.3 42.3 42.3 <![CDATA[INDOPOL TM H100 (after curing) (phr)]]> 22.0 22.0 22.0 Total (phr) 221.1 216.8 205.1
[0329] Table 2 shows the physical properties of Example E1. Table 2 includes specific gravity, water vapor, extrusion surface, hardness (Shore A), tensile, compression set, and permeability of E1. Comparative Example C1 is an elastomer comprising a brominated isobutylene-p-methylstyrene terpolymer, EXXPRO TM Specialty Elastomer Grade 3433 is used herein as a performance reference for pharmaceutical thermoset rubber formulations.
[0330] Table 2. Physical properties
[0331] E1 C1 Specific gravity (22.7℃) 0.9571 Water vapor (%) 0.0245 Ceast (LCR at 1200 1 / s) 118.229 Extrusion surface Ra (μm) 160 Hardness (ISO) Shore A 75 46 Tensile strength M100 (MPa) 4 1.5 Tensile UTS(MPa) 16 4.5 Stretching UE (%) 360 550 <![CDATA[Permeability (cc.mm / m 2 .day.mmHg)]]> 0.458 0.3
[0332] In order to evaluate the closure performance of the thermoplastic elastomer composition and determine whether it can meet or exceed the requirements of USP 381 Type I-II for elastomeric closures, a pharmaceutical application performance test (see Table 3) was carried out. Such performance tests will help to determine the acceptable elastomeric closures (i.e., plugs) for injection preparations based on their biological reactivity, the physicochemical properties of their water extracts, and their functions. The pharmaceutical application performance test was carried out on Example E1. Comparative Example C2 is a combination of the required performance characteristics described in the United States Pharmacopoeia Guide (USP 381). Punch force, self-sealing and fragmentation performance are measured according to the method specified in USP 381. Thermoplastic elastomer composition E1 reaches acceptable fragmentation performance, thus meeting the requirements of USP381 Type I and II for elastomeric closures.
[0333] Table 3. Drug application performance test
[0334]
[0335] Table 4 shows the formulations of amine-cured thermoplastic elastomer compositions E4-E6.
[0336] Amine Cure-2: A chemical containing dicinnamylenediamine, available from Vanderbilt Chemicals.
[0337] Amine Cure-3: A chemical containing (6-aminohexyl)carbamic acid available from Vanderbilt Chemicals.
[0338] The terpolymer content in all formulations (Examples E4-E6) was 100 phr, and INDOPOL TM The total content of H100 is 64.3 phr. C3 is a control compound for comparison purposes. Comparative Example C3 is a thermoplastic elastomer composition comprising the same amount of BIMSM-2 (100 phr) and PP-1 (30 phr) as the thermoplastic elastomer compositions E4-E6 of the present invention. Comparative Example C3 differs from the thermoplastic elastomer compositions E4-E6 in the curing system: C3 is cured using a phenolic resin-based curing system.
[0339] Table 4. Amine-based curing systems: blend compositions and conditions
[0340] preparation C3 E4 E5 E6 BIMSM-2(phr) 100.00 100.00 100.00 100.00 PP-1(phr) 30.00 30.00 30.00 30.00 <![CDATA[ICECAP TM Clay (phr)]]> 10.00 10.00 10.00 10.00 <![CDATA[INDOPOL TM H100 (before curing) (phr)]]> 42.30 42.30 42.30 42.30 <![CDATA[INDOPOL TM H100 (after curing) (phr)]]> 22.00 22.00 22.00 22.00 Zinc oxide (phr) 5.00 <![CDATA[Phenolic resin SP-1045 TM (phr)]]> 5.00 Amine curing - 1(phr) 1.75 Amine curing - 2(phr) 2.25 Amine cure - 3(phr) 1.10 Total (phr) 214.30 206.05 206.55 205.4
[0341] Table 5 shows the physical properties of the unaged thermoplastic elastomer compositions E4-E6. Table 5 includes the hardness (Shore A), tensile strength, elongation, and specific gravity of Examples E4-E6. As shown in Table 5, the physical properties required for pharmaceutical stopper applications are achieved with thermoplastic elastomer compositions E4-E6, wherein E4-E6 provides suitable melt flow and injection molding properties for pharmaceutical products.
[0342] Table 5. Physical properties of unaged thermoplastic elastomer compositions for amine-based cure systems
[0343]
[0344] Sample preparation using a twin screw extruder (TSE)
[0345] Unless otherwise stated, the following description explains the method adopted for the following samples. According to the method described in the United States Patent No. 4,594,391 and US 2011 / 0028637 (except the conditions of the changes determined herein), the co-rotating fully intermeshing twin screw extruder provided by Coperion Corporation, Ramsey NJ is used. BIMSM is fed to the feed throat of the ZSK 53 extruder having a L / D (length of the extruder compared to its diameter) of about 44. Thermoplastic resin (polypropylene, and soft thermoplastic elastomer phase (if present)) is also fed to the feed throat, and other reaction rate control agents (such as fillers, such as talcum) are added to the feed throat of the extruder at the same time. Processing oil is injected into the extruder at multiple positions along the extruder. After rubber, thermoplastic and filler begin to blend and after introducing the first processing oil (precuring oil), curing agent is injected into the extruder. In some embodiments, the curing agent is injected with a process oil, which may be the same or different from other oils introduced into the extruder or the oil that stretches the rubber. The process oil may be injected at more than one location along the extruder. The initiation and control of the rubber crosslinking reaction is performed by balancing a combination of viscous heat generated by shear application, barrel temperature set point, use of catalyst, and residence time.
[0346] Unless specified, the extrusion material is fed into the extruder at a rate of 70 kg / hour, and extrusion mixing is performed at 325 revolutions per minute (RPM). The barrel starts from barrel section 2 and moves toward the bottom of the die until barrel section 12, and the barrel metal temperature curve (in ° C) used is 160 ° C / 160 ° C / 160 ° C / 160 ° C / 165 ° C / 165 ° C / 165 ° C / 165 ° C / 180 ° C / 180 ° C / 180 ° C (where the last temperature value is for the die). Low molecular weight contaminants, reaction by-products, residual moisture, etc. are removed by ventilation through one or more vents, usually under vacuum as needed. The final product is filtered by using a melt gear pump and a filter screen of the desired mesh size. A screw design with multiple mixing sections was used, which included a combination of forward conveying sections, intermediate sections, left-handed kneading blocks, and left-handed conveying elements to mix the process oil, curing agent, and provide sufficient residence time and shear to complete the curing reaction without slipping or surging in the extruder.
[0347] Table 6 shows the compositions of the inventive TPV compositions that provide an excellent balance of processability, punchability, resealability, and tensile properties.
[0348] MgO: is a high purity, lightly calcined, high surface area, very reactive magnesium oxide. It is primarily used to neutralize acids formed during processing of elastomeric compounds. This high quality magnesium oxide is produced by a precisely controlled seawater extraction process that produces a consistent unique crystal morphology and very narrow particle size distribution for use in applications requiring fast reaction rates. Available from Hallstar under the trade name MAGLITE D (RX-13856).
[0349] HCR: A hydrocarbon resin with a softening point of 137.7°C, used as a performance modifier resin for blending with polymers. Available from ExxonMobil under the trade name Oppera.
[0350] OBC-1: An olefin block copolymer composite comprising an ethylene-propylene (EP) copolymer, an isotactic polypropylene (iPP) and an EP-iPP diblock polymer; melt flow rate (230°C, 2.16 kg) of 7 g / 10 min, a total ethylene content of 29 wt%, a tensile stress at break of 10.8 MPa, and a Vicat softening point of 124°C; available from Dow under the trade name Intune.
[0351] OBC-2: OBC consists of crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, the crystallizable ethylene-octene blocks having less than 10 wt% α-olefin comonomer content and a melting point greater than 90°C, the low crystallinity ethylene-octene blocks having greater than 10 wt% comonomer content and a melting point less than 90°C. This gives the polymer better high temperature resistance and elasticity than typical metallocene random polymers of similar density. Available from Dow under the trade name Infuse; density 0.877 g / cm 3 , melting point T m The hardness is 122°C, the Shore A hardness is 69, the ultimate tensile strength at break is 10 MPa, and the compression set at 70°C is 55%.
[0352] Polybutene oil: is a low molecular weight polybutene polymer with a number average molecular weight Mn of 910 g / mol according to GPC, a flash point > 210°C and a viscosity index of 125. Available under the trade name Indopol.
[0353] Table 6. Blend composition
[0354] preparation E7 E8 E9 E10 E11 E12 E13 E14 E15 E16 E17 BIMSM-2 100 100 100 100 100 100 100 100 100 100 100 talc 5 5 5 5 5 5 5 5 5 5 5 MgO 2 2 2 2 2 2 2 2 2 2 2 HCR 20 PP-2 8 8 8 8 8 8 16 8 8 16 8 OBC-1 37 45 50 37 15 OBC-2 37 40 50 55 60 44 37 Polybutene oil 40 40 40 60 70 70 50 65 65 60 Amine Curing-1 2 2 2 2 2 2 2 2 2 2 2 Total (phr) 194 194 177 207 222 237 232 222 242 234 229
[0355] Test method:
[0356] Shore A hardness is measured according to ISO 868 at 15 second intervals and / or according to ASTM D-2240 at 5 second intervals;
[0357] M100 is measured according to ASTM D-412;
[0358] Tensile strength was measured according to ASTM D-412;
[0359] Elongation at break was determined according to ASTM D-412;
[0360] Stress at 100% strain was determined according to ASTM D-412;
[0361] Tensile set was measured according to ASTM D-412 at room temperature after 100% elongation;
[0362] Compression set was measured according to ASTM D-395 Method B at room temperature, 70°C, and 100°C;
[0363] LCR Viscosity Use The capillary rheometer was measured at 1200 l / s and 202°C.
[0364] O2 gas permeability is measured according to ISO 2782-1:2012 (E), where the thickness of each sample is measured at 5 points evenly distributed over the sample penetration area. The test specimen is bonded to the support with a suitable adhesive that cures at the test temperature. The chamber is evacuated by drawing a vacuum on both sides of the membrane. The high pressure side of the membrane is exposed to the test pressure of O2 gas at 23°C and 40°C. The test pressure and temperature are maintained throughout the test, and the temperature and pressure are recorded regularly. The sample is placed under pressure until a steady-state permeation is reached (3-5 times the time lag).
[0365] The punching force, self-sealing and fragmentation properties were measured according to the methods specified in the United States Pharmacopeia (USP) 381 "Elastomeric Closures for Injection". The surface roughness was tested on a Model Perthometer S2 surface measuring device.
[0366] Table 7 shows the properties of the TPV composition of the present invention that can be used as a pharmaceutical plug. The TPV composition exhibits excellent processing properties, as shown by the low LCR viscosity data of less than 300 Pa.s at 1200 1 / s, which is common in injection molding applications, indicating that the material can be successfully injection molded into a pharmaceutical plug under selected conditions. In addition, as shown in Table 7, the TPV composition exhibits excellent compression deformation, less than 20% at room temperature and less than 30% at 70°C. This is very important to ensure that the sealing is not compromised when converting from a thermoset plug to an injection molded TPV plug. In addition, the TPV plug exhibits excellent oxygen barrier properties comparable to the thermoset Exxpro plug.
[0367] Table 7. Physical properties
[0368]
[0369] Figure 1 Tests related to the properties of pharmaceutical stoppers are shown. TPV stoppers need to meet certain requirements related to self-sealing, crushing and punching force in order to be used in pharmaceutical applications. Figure 1 As shown, the TPV compositions of the present invention shown above exhibit excellent self-sealing comparable to Exxpro thermoset materials. Importantly, it was observed that the TPV compositions had very low chipping and punching forces, indicating that the needle can easily penetrate the septum or plug without leaving any rubber particles on the needle.
[0370] The stress relaxation slope is measured in compression using an Elastocon stress relaxation tester according to ISO 3384A. The samples are laminated to a thickness of up to 2 mm and compressed to 10% deflection at 70°C for 24 hours. A normalized pressure graph as a function of time is constructed (normalized relative to the pressure at @t=0.01s). The slope of the graph is defined as the stress relaxation slope in l / min. Figure 2 and Figure 3 It was shown that stress relaxation was improved compared to compositions without the soft thermoplastic elastomer and was comparable to that of the thermoset Exxpro alone.
[0371] In the remaining embodiments, different thermoplastic vulcanizate articles are provided, each of which comprises a soft thermoplastic elastomer. Each of these embodiments provides an injection moldable thermoplastic vulcanizate with performance properties suitable for use in medical stoppers and comparable to the non-injection moldable thermoset Exxpro.
[0372] Sample preparation using a Brabender mixer
[0373] Thermoplastic vulcanizate is prepared by vulcanizing with amine curing agent using conventional procedures in a Brabender mixer to dynamically vulcanize elastomeric copolymers. Specifically, thermoplastic vulcanizate is prepared in a laboratory Brabender-Plasticorder (model EPL-V5502). The capacity of the mixing tank is 85ml, using a cam-type rotor. Rubber is initially added to a mixing tank heated to 180°C and a rotor speed of 100rpm. Subsequently, plastics (usually in pellet form) and talcum are loaded into a mixer and melt-mixed for two minutes. Then polybutene oil (precuring oil) is added dropwise within one minute, and mixing continues for 1 to 5 minutes (at this time, stable torque is obtained), and then phenolic resin is added. Then the amine curing agent is added to the mixing tank, followed by the addition of stannous chloride MB, and the motor torque increases due to the occurrence of the curing reaction.
[0374] Mixing was continued for about 4 more minutes, after which the molten TPV was removed from the mixer and extruded into sheets while hot between polytetrafluoroethylene plates, which were cooled, cut and compression molded at about 400°F. A Wabash press (model 12-1212-2TMB) was used for compression molding, with a 4-cavity polytetrafluoroethylene-coated mold having a mold cavity size of 4.5"x4.5"x0.06" mold. The material in the mold was initially preheated on a 4" plunger at 2 tons of pressure at about 400°F (204.4°C) for about 2 to 2.5 minutes, then the pressure was increased to 10 tons and heating continued for about 2 to 2.5 minutes more. The mold platens were then cooled with water, and the mold pressure was released after cooling (about 70°C).
[0375] The clay used was a calcined clay available under the trade name Polestar.
[0376] PP-3: Homopolymer resin designed for spunbond nonwoven fabrics. The density of the resin is 0.90g / cm 3 , melt flow rate 36 g / 10 min (230° C., 2.16 kg). Available from ExxonMobil.
[0377] PBE-1: mainly composed of isotactic propylene repeating units with random ethylene distribution and produced using a metallocene catalyst. The density of the sample is 0.862 g / cm 3 , melt index (190°C / 2.16kg) is 9.1 g / 10 min, ethylene content is 15 wt%, Shore A hardness is 64, and tensile strength at break is 5.5 MPa (ASTM D412). It can be obtained from ExxonMobil.
[0378] PBE-2: mainly composed of isotactic propylene repeating units with random ethylene distribution and produced using a metallocene catalyst. The density of the sample is 0.873 g / cm 3 , a melt index (190°C / 2.16kg) of 3.7 g / 10 min, an ethylene content of 11 wt%, a Shore D hardness of 27, and a tensile strength at break of 14 MPa (ASTM D412). It can be obtained from ExxonMobil.
[0379] Table 8. Blend composition
[0380] preparation E18 E19 E20 BIMSM-2 100 100 100 clay 10 10 10 Polybutene oil 64.3 64.3 64.3 PP-3 37 26 26 PBE-1 11 PBE-2 11 Amine Curing-1 3.5 3.5 3.5 Total (phr) 214.8 214.8 214.8
[0381] Table 9. Physical properties
[0382]
[0383] Table 10. Physical properties
[0384]
[0385] Pharmaceutical compositions containing various thermoplastic resins
[0386] The following examples contain only soft thermoplastic elastomer in the thermoplastic phase
[0387] COC-1:TOPAS TM 8007. Commercial cyclic olefin copolymer, density 1010 kg / m 3 (ISO 1183), melt volume rate (190℃ / 2.16kg) is 2cm 3 / 10 min (ISO1133), a glass transition temperature of 78°C (10°C / min, ISO11357-1, ISO11357-2, ISO11357-3), and a nominal norbornene content of 66 wt%-68 wt%.
[0388] 4MP-1 is a 4-methyl-1-pentene / propylene copolymer with a melt flow rate of 10 g / 10 min (230° C., 2.16 kg). The copolymer has a Shore D hardness of 55, a tensile strength at break of 30 MPa, a Tg of 40° C. as measured by DSC, and a melting point of 130° C. The copolymer is marketed under the trade name Absortomer TM Available from Mitsui Chemicals.
[0389] PE-1 is a pipe extrusion grade HDPE copolymer with excellent stiffness and stress crack resistance. The density of PE-1 is 0.953g / cm 3 , the melt index is 0.25 g / 10 min (190° C. / 2.16 kg), the yield tensile strength is 28 MPa, and the flexural modulus is 970 MPa.
[0390] MB1: Anhydrous SnCl2 masterbatch with polypropylene homopolymer and SnCl2 (45 wt%).
[0391] ZnO: A commercial ZnO cure modifier / acid scavenger sold under the trade name Kadox TM 911 available.
[0392] Phenolic Resin: Phenolic resin is octylphenol-formaldehyde resin.
[0393] Clay: Trade name Icecap TM Calcined clay obtained from Burgess K Clay TM available).
[0394] Table 11. Blend composition
[0395]
[0396] Table 12. Physical properties
[0397]
[0398] Table 13. Physical properties
[0399]
[0400] Pharmaceutical compositions containing thermoplastic blends
[0401] 4MP-21 is a 4-methyl-1-pentene / propylene copolymer with a melt flow rate of 10 g / 10 min (230°C, 2.16 kg) and a density of 0.840 g / cm 3 The Shore A hardness is 70, the tensile strength at break of the copolymer is 27 MPa, the Tg measured by DSC is 30°C, and the melting point cannot be detected. TM Available from Mitsui Chemicals.
[0402] Table 14. Blend composition
[0403]
[0404] Table 15. Physical properties
[0405]
[0406] Table 16. Physical properties
[0407]
[0408] Styrene / isobutylene / styrene elastomers as blends
[0409] SIBS-1: is a triblock copolymer of styrene / isobutylene / styrene. The copolymer has a Shore A hardness of 25, a melt flow rate of 0.6 g / 10 min (230° C., 2.16 kg), a tensile strength of 15 MPa, and a compression set of 65% at 70° C.
[0410] SIBS-2: is a triblock copolymer of styrene / isobutylene / styrene. The copolymer has a Shore A hardness of 46, a melt flow rate of 0.1 g / 10 min (230° C., 2.16 kg), a tensile strength of 18 MPa, and a compression set of 50% at 70° C.
[0411] Table 17. Blend composition
[0412]
[0413] Table 18. Physical properties
[0414]
[0415] All documents described herein are incorporated herein by reference, including any priority documents and / or testing procedures consistent with this article. It is apparent from the general description and specific embodiments above that, although some embodiments have been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is not intended to be limited thereby. Likewise, the term "comprising" is considered to be synonymous with the term "including". Likewise, whenever there is a transitional phrase "comprising" in front of a composition, an element, or a group of elements, it can be understood that we also consider the same composition or a group of elements with a transitional phrase "essentially consisting of...", "consisting of...", "selected from a group consisting of..." or "is" before the narration of the composition or one or more elements, and vice versa.
Claims
1. A thermoplastic elastomer composition comprising: One or more brominated isobutylene-p-methyl-styrene terpolymers; and 10 to 80 parts by weight per hundred parts by weight of rubber (phr) of a polypropylene homopolymer; wherein the thermoplastic elastomer composition is cured using a sulfur-based curing system or an amine-based curing system; wherein the composition exhibits a compression set at 70°C of <35%.
2. The thermoplastic elastomer composition according to claim 1, wherein The polypropylene homopolymer is present at 20 to 40 phr.
3. The thermoplastic elastomer composition according to claim 1, wherein Process oil is present at 10 to 100 phr.
4. The thermoplastic elastomer composition according to claim 3, wherein The process oil comprises a polyisobutylene polymer.
5. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein The sulfur-based curing system comprises a sulfur curing agent, and the sulfur curing agent comprises one or more of the following: 0.1phr to 10phr MBTS; 0.01 to 5 phr of sulfur; 0.1 to 10 phr of metal oxides; and 0.5 to 15 phr of stearic acid.
6. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein The amine-based curing system comprises one or more amine curing agents present in an amount of 0.1 to 10 phr, and wherein the one or more amine curing agents are selected from (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
7. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein The composition exhibits one or more of the following properties: 0.8g / cm 3 Up to 1g / cm 3 Specific gravity at 23°C; 0.01% to 0.03% water vapor (%); Extrusion surface Ra (μm) of 140 to 190; Tensile strength (MPa) from 1 to 10; 100% modulus (MPa) from 1 to 5; Elongation at break of 100 to 500%; or 0.1 to 1 permeability (cc.mm / m 2 .day.mmHg).
8. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein The thermoplastic elastomer composition has a hardness (Shore A) of 20 to 90.
9. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein The thermoplastic elastomer composition is at least partially crosslinked.
10. A thermoplastic vulcanized rubber composition comprising: an elastomeric phase comprising one or more brominated isobutylene-p-methyl-styrene terpolymers; 10 to 90 parts by weight per hundred parts by weight of rubber (phr) of a thermoplastic phase comprising a blend of one or more thermoplastic polyolefins and one or more soft thermoplastic elastomers, wherein the soft thermoplastic elastomer has a Shore A hardness of 20 to 96, a Shore D hardness of 20 to 50, and a tensile strength at break of 2 MPa to 20 MPa; and 10phr to 100phr of process oil; wherein the elastomeric phase is cured using an amine-based cure system and the composition exhibits a compression set at 70°C of <35%.
11. The thermoplastic vulcanized rubber composition according to claim 10, wherein The one or more soft thermoplastic elastomers comprise an olefin-based block copolymer comprising crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, wherein the crystallizable ethylene-octene blocks have an α-olefin comonomer content of less than 10 wt% and a melting point greater than 90°C, and the low crystallinity ethylene-octene blocks have a comonomer content of greater than 10 wt% and a melting point less than 90°C.
12. The thermoplastic vulcanized rubber composition according to claim 10, wherein: The one or more soft thermoplastic elastomers comprise a propylene-based olefin block copolymer (OCP) blend comprising an ethylene-propylene (EP) copolymer, an isotactic polypropylene (iPP), and an EP-iPP diblock polymer.
13. The thermoplastic vulcanized rubber composition according to claim 10, wherein: The one or more soft thermoplastic elastomers include a styrene-isobutylene styrene (SIBS) polymer.
14. The thermoplastic vulcanized rubber composition according to claim 10, wherein: The one or more soft thermoplastic elastomers comprise a propylene-based elastomer comprising units derived from a major portion of propylene and 5 wt% to 25 wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins.
15. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The one or more soft thermoplastic elastomers comprise a 4-methyl-1-pentene / α-olefin copolymer comprising 50 to 100 wt % of structural units derived from methyl-1-pentene, and 0 to 50 wt % of structural units derived from at least one olefin selected from olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene.
16. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The one or more soft thermoplastic elastomers include one or more of the following: (1) an olefin-based block copolymer comprising crystallizable ethylene-octene blocks alternating with low crystallinity ethylene-octene blocks, wherein the crystallizable ethylene-octene blocks have an α-olefin comonomer content of less than 10 wt% and a melting point of greater than 90°C, and the low crystallinity ethylene-octene blocks have a comonomer content of greater than 10 wt% and a melting point of less than 90°C, (2) a propylene-based olefin block copolymer (OCP) blend comprising an ethylene-propylene (EP) copolymer, an isotactic polypropylene (iPP) and an EP-iPP diblock polymer, (3) Styrene-isobutylene styrene (SIBS) polymer, (4) a propylene-based elastomer comprising units derived from a major portion of propylene and from 5 wt% to 25 wt% of one or more comonomers selected from ethylene and / or C4-C12 α-olefins, and (5) a 4-methyl-1-pentene / α-olefin copolymer comprising 50% by weight to 100% by weight of a structural unit derived from 4-methyl-1-pentene, and 0% by weight to 50% by weight of a structural unit derived from at least one olefin selected from olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene, or any combination thereof.
17. The thermoplastic vulcanizate rubber composition according to any one of claims 10 to 16, wherein The one or more thermoplastic polyolefins include a propylene-based polymer, an ethylene-based thermoplastic polymer, a polypropylene homopolymer (PPH), or any combination thereof.
18. The thermoplastic vulcanizate rubber composition according to claim 11, wherein The olefin-based block copolymers exhibit one or more of the following properties: (1) a melt flow rate (MFR) of 0.5 g / 10 min to 30 g / 10 min at 190° C. and 2.16 kg load, (2) Melting temperature of 100°C to 130°C, (3) Shore A hardness of 30 to 95, or (4) Tensile strength of 1.5 MPa to 18 MPa.
19. The thermoplastic vulcanizate rubber composition according to claim 12, wherein: The propylene-based olefin block copolymer (OBC) blends exhibit one or more of the following properties: (1) a melt flow rate (MFR) of 0.5 g / 10 min to 100 g / 10 min at 230°C and 2.16 kg load based on ASTM D1238 test method, (2) Shore A hardness of 30 to 98, (3) Shore D hardness of 5 to 60, (4) 90 wt% to 15 wt% ethylene content, (5) Vicat softening point between 20°C and 150°C, or (6) Tensile strength at break of 1.5 MPa to 20 MPa.
20. The thermoplastic vulcanizate rubber composition according to claim 13, wherein: The styrene-isobutylene styrene (SIBS) polymer exhibits one or more of the following properties: (1) a melt flow rate (MFR) of 0.05 g / 10 min to 30 g / 10 min at 230° C. and 2.16 kg load, (2) Tensile strength at break from 4MPa to 25MPa, (3) Shore A hardness of 15 to 60, or (4) Compression set at 70°C of 30% to 120%.
21. The thermoplastic vulcanizate rubber composition according to claim 14, wherein: The propylene-based elastomer exhibits one or more of the following properties: (1) a melt flow rate (MFR) of 0.2 g / 10 min to 25 g / 10 min at 190° C. and 2.16 kg load, (2) an ethylene content of 1 wt% to 25 wt%, or (3) Melting temperature of 20°C to 110°C.
22. The thermoplastic vulcanizate rubber composition according to claim 15, wherein: The 4-methyl-1-pentene / α-olefin copolymer exhibits one or more of the following characteristics: (1) a melt flow rate (MFR) of 0.5 g / 10 min to 20 g / 10 min at 230° C. and 2.16 kg load, (2) A tensile strength at break of 20 MPa to 30 MPa, or (3) Glass transition temperature (Tg) of -10°C to 50°C.
23. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The elastomeric phase is cured using an amine curing system comprising one or more amine curing agents present in an amount of 0.1 to 10 phr, and wherein the one or more amine curing agents are selected from (6-aminohexyl)carbamic acid, N,N'-dicinnamylene-1,6-hexamethylenediamine, 4,4'-methylenebis(cyclohexylamine)carbamate, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylallyl isocyanurate, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N-diethyl-p-phenylenediamine.
24. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The curing system is substantially free of heavy metal components, phenolic resins, or sulfur.
25. The thermoplastic vulcanizate composition according to claim 10, wherein: The process oil comprises a polyisobutylene polymer.
26. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The process oil comprises a styrene-isobutylene styrene polymer.
27. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The process oil comprises a propylene-based elastomer comprising units derived from a major portion of propylene and from 5 wt% to 25 wt% of one or more comonomers selected from ethylene and / or C4-C12 alpha-olefins.
28. The thermoplastic vulcanizate composition of claim 10, further comprising a cyclopentadiene-based hydrocarbon resin having a glass transition temperature (Tg) greater than 20°C.
29. The thermoplastic vulcanizate rubber composition according to claim 10, wherein: The elastomeric phase is at least partially crosslinked.
30. The thermoplastic vulcanizate composition according to claim 10, wherein: The composition exhibits one or more of the following properties: (1) Shore A hardness of 20 to 90, (2) Tensile strength at break from 1.5 MPa to 8 MPa, (3) Compression set at 70°C of less than 35%, or (4) Oxygen permeability measured at 40°C of <0.2cc*mm / (m2-day-mmHg).
31. A medical stopper comprising the thermoplastic vulcanized rubber composition according to any one of claims 10 to 30.
Citation Information
Patent Citations
Isobutylene-based polymer and process of producing the same
EP0731112A2
Resin composition and member comprising said resin composition
EP1431343A1
Thermoplastic elastomer composition
EP1561783A1
Thermoplastic elastomer composition
EP1566405A1
Catalyst composition comprising shuttling agent for ethylene multi-block copolymer formation
US20070167578A1
